Polyamide resin composition

By controlling the particle morphology of brominated flame retardants and combining them with a polyamide resin composition of a specific composition, the problem of bubbling in flame-retardant polyamide resin molded articles during the reflow soldering process was solved, achieving excellent bubbling resistance at high temperatures.

CN121693541APending Publication Date: 2026-03-17KURARAY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202480051734.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-08-10
Filing Date
2024-08-09
Publication Date
2026-03-17

AI Technical Summary

Technical Problem

Flame-retardant polyamide resin molded parts are prone to blistering when exposed to high temperatures during reflow soldering, especially those containing colorants, which have a higher blistering rate. Existing technologies have not been able to effectively solve this problem.

Method used

A polyamide resin composition containing polyamide with a melting point above 280℃, brominated flame retardant, inorganic filler, aromatic vinyl copolymer and colorant is used. The particle morphology of the brominated flame retardant is controlled. By limiting parameters such as the cross-sectional area and Freret diameter ratio of the particles, the expansion of the particles and the interface damage at high temperature are reduced.

Benefits of technology

The foaming resistance of the flame-retardant polyamide resin molded parts was significantly improved during the reflow soldering process, and the foaming at high temperatures was suppressed, ensuring the stability of the molded parts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121693541A_ABST
    Figure CN121693541A_ABST
Patent Text Reader

Abstract

The present invention provides a polyamide resin composition containing (A) a polyamide having a melting point of 280 DEG C or higher, (B) a brominated flame retardant, (C) an inorganic filler, (D) an aromatic vinyl copolymer, and (E) a colorant, the polyamide (A) containing a diamine unit, 50-100 mol% of the diamine unit being an aliphatic diamine unit having 4-18 carbon atoms, when particles of the brominated flame retardant (B) in a specific region in a thickness-direction cross-section of a test piece containing the polyamide resin composition are observed, Rs1 represented by formula (bs / as) As is less than 0.2 [mu] m2. [In the formula, bs / as is the number average value of the ratio of the vertical Feret diameter to the minimum Feret diameter among the Feret diameters of the particles of the brominated flame retardant (B) observed in the region, and As is the number average value ([mu] m2) of the cross-sectional area of the particles of the brominated flame retardant (B) observed in the region. ]
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to a polyamide resin composition. Specifically, it relates to a polyamide resin composition and a method for producing the same, and a molded body of the polyamide resin composition. BACKGROUND

[0002] Polyamide resins are used for various applications such as automobile parts, electrical and electronic parts, and the like, because of their excellent mechanical properties, heat resistance, and the like. In addition, halogen-based flame retardants, such as bromine-based flame retardants, are sometimes compounded in polyamide resin compositions as flame retardants (see Patent Documents 1 to 4). Polyamide resin compositions in which the flame retardancy is thus improved are also referred to as flame-retardant polyamide resin compositions.

[0003] PRIOR ART DOCUMENTS

[0004] PATENT DOCUMENTS

[0005] Patent Document 1: International Publication No. 2020 / 040191

[0006] Patent Document 2: Japanese Patent Application Publication No. 2002-138197

[0007] Patent Document 3: Japanese Patent Application Publication No. 2000-186206

[0008] Patent Document 4: Japanese Patent Application Publication No. 2007-291250 SUMMARY

[0009] PROBLEMS TO BE SOLVED BY THE INVENTION

[0010] If a molded body of a flame-retardant polyamide resin composition (hereinafter, also referred to as "flame-retardant polyamide resin molded body", and according to circumstances, also simply referred to as "molded body") is exposed to high temperatures in a reflow soldering process, the inside and the surface of the molded body sometimes expand, i.e., blistering occurs. However, in Patent Documents 1 to 4, the above-mentioned blistering is not sufficiently studied.

[0011] In addition, flame-retardant polyamide resin compositions are sometimes colored and used for the above-mentioned automobile part applications, applications toward electrical and electronic parts. The results of the research by the present inventors and the like have clarified that if a molded body of a flame-retardant polyamide resin composition containing a colorant is exposed to high temperatures in a reflow soldering process, there is a tendency that the occurrence rate of blistering becomes higher.

[0012] Therefore, there is a need for a flame-retardant polyamide resin composition that can obtain a flame-retardant polyamide resin molded body in which the occurrence rate of blistering even when exposed to high temperatures in a reflow soldering process is low, i.e., the blistering resistance is excellent.

[0013] Therefore, the object of the present invention is to provide a polyamide resin composition capable of producing a flame-retardant polyamide resin molded body with excellent foaming resistance even when exposed to high temperatures during a reflow soldering process, a method for manufacturing the polyamide resin composition, and a molded body of the polyamide resin composition.

[0014] Methods for solving problems

[0015] In order to solve the above-mentioned problem, the inventors conducted in-depth research and came up with the following invention, which found that it can solve the problem.

[0016] That is, the present invention is as follows.

[0017] [1] A polyamide resin composition comprising a polyamide (A) with a melting point of 280°C or higher, a brominated flame retardant (B), an inorganic filler (C), an aromatic vinyl copolymer (D), and a colorant (E).

[0018] The polyamide (A) described above contains diamine units, wherein 50 to 100 mol% of the diamine units are aliphatic diamine units having 4 to 18 carbon atoms.

[0019] The aforementioned colorant (E) is at least one of organic and inorganic colorants.

[0020] When observing the particles of the brominated flame retardant (B) in a cross-section along the thickness direction of a test piece containing the above-described polyamide resin composition (30 mm in length, 10 mm in width, and 1.0 mm in thickness), in a region with a depth of 250 μm ± 8.8 μm from the main surface of the test piece and a width of 25 μm orthogonal to the thickness direction, the number average cross-sectional area As (μm²) of the particles of the brominated flame retardant (B) is as follows: 2 Less than 0.1μm 2 .

[0021] [2] According to the polyamide resin composition described in [1], when the particles of the brominated flame retardant (B) in the above-mentioned region are observed, the product of the average value EqD of the diameter of a circle having the same area as the cross-sectional area of ​​the particles of the brominated flame retardant (B) and the circumference of the circle, i.e., EqD×π (μm), is less than 1.0 μm.

[0022] [3] A polyamide resin composition comprising polyamide (A) with a melting point above 280°C, brominated flame retardant (B), inorganic filler (C), aromatic vinyl copolymer (D), and colorant (E).

[0023] The polyamide (A) described above contains diamine units, wherein 50 to 100 mol% of the diamine units are aliphatic diamine units having 4 to 18 carbon atoms.

[0024] The aforementioned colorant (E) is at least one of organic and inorganic colorants.

[0025] When observing the particles of the brominated flame retardant (B) in a cross-section along the thickness direction of a test piece containing the above-mentioned polyamide resin composition (30 mm in length, 10 mm in width, and 1.0 mm in thickness), in a region with a depth of 250 μm ± 8.8 μm from the main surface of the test piece and a width of 25 μm orthogonal to the thickness direction, Rs1 (μm) as shown in the following formula (1) 2 Less than 0.2μm 2 .

[0026] Rs1=(bs / as)×As (1)

[0027] In equation (1),

[0028] bs / as is the numerical average of the ratios of the vertical Ferrette diameters of the particles of brominated flame retardant (B) observed in the aforementioned region to the minimum Ferrette diameter, and...

[0029] As is the number average (μm) of the cross-sectional area of ​​brominated flame retardant (B) particles observed in the above region. 2 ).

[0030] [4] According to the polyamide resin composition described in [3], when observing the particles of the above-mentioned brominated flame retardant (B) in the above-mentioned region, the Rs2 (μm) shown in the following formula (2) is less than 1.7 μm.

[0031] Rs2=(bs / as)×EqD×π (2)

[0032] In equation (2),

[0033] bs / as is the numerical average of the ratios of the vertical Ferrette diameters of the particles of brominated flame retardant (B) observed in the aforementioned region to the minimum Ferrette diameter, and...

[0034] EqD is the numerical average (μm) of the diameter of a perfect circle having the same area as the cross-sectional area of ​​the brominated flame retardant (B) particles observed in the aforementioned region.

[0035] [5] The polyamide resin composition according to any one of [1] to [4], wherein ΔE represented by the following formula (X) is greater than 1.

[0036] [Mathematical Expression 1]

[0037] ... (X)

[0038] [In equation (X), ΔE is derived from CIE1976 (L * a * b * The color difference specified in the color system, L * col a * col and b * col The above-mentioned polyamide resin composition is derived from CIE1976 (L * a * b * The color system specified by L * a * and b * L * nat a * nat and b * nat It is a colorless polyamide resin composition that has the same composition as the above-described polyamide resin composition except that it does not contain colorant (E), according to CIE 1976 (L). * a * b * The color system specified by L * a * and b * 。

[0039] [6] The polyamide resin composition according to any one of [1] to [5], wherein the organic colorant is selected from at least one of anthraquinone dyes, violet ketone dyes, anthraquinone dyes and phthalocyanine dyes.

[0040] [7] The polyamide resin composition according to any one of [1] to [6], wherein the inorganic colorant is selected from at least one of carbon black, metal oxide, metal sulfide and composite metal oxide.

[0041] [8] The polyamide resin composition according to any one of [1] to [7], wherein the inorganic colorant is selected from at least one of metal oxides, metal sulfides and composite metal oxides.

[0042] [9] The polyamide resin composition according to any one of [1] to [8], wherein the colorant (E) comprises the organic colorant, the content of which is 0.0001 to 0.5% by mass relative to 100% by mass of the polyamide resin composition.

[0043]

[10] The polyamide resin composition according to any one of [1] to [9], wherein the colorant (E) comprises the inorganic colorant, and the content of the inorganic colorant is 0.001 to 5.0% by mass relative to 100% by mass of the polyamide resin composition.

[0044]

[11] The polyamide resin composition according to any one of [1] to

[10] , wherein the brominated flame retardant (B) is selected from at least one of brominated polystyrene and polybrominated polystyrene.

[0045]

[12] The polyamide resin composition according to any one of [1] to

[11] , wherein the polyamide (A) comprises a dicarboxylic acid unit, wherein 50 mol% or more of the dicarboxylic acid unit is a terephthalic acid unit, and the aliphatic diamine constituting the aliphatic diamine unit having 4 to 18 carbons is at least one selected from 1,4-butanediamine, 1,6-hexanediamine, 1,9-nonanediamine, 2-methyl-1,8-octanediamine and 1,10-decanediamine.

[0046]

[13] According to the polyamide resin composition described in

[12] , wherein the aliphatic diamine having 4 to 18 carbon atoms is selected from at least one of 1,9-nonanediamine and 2-methyl-1,8-octanediamine.

[0047]

[14] The polyamide resin composition according to any one of [1] to

[13] , wherein the aromatic vinyl copolymer (D) comprises at least one structural unit derived from styrene and α-methylstyrene, and at least one structural unit derived from maleic anhydride and monoalkyl maleic anhydride having 1 or more and 3 or fewer carbon atoms.

[0048] The glass transition temperature of the above-mentioned aromatic vinyl copolymer (D) is above 120°C.

[0049]

[15] According to the polyamide resin composition described in

[14] , the content of at least one structural unit in the above-mentioned aromatic vinyl copolymer (D) derived from maleic anhydride and monoalkyl maleic anhydride having 1 or more and 3 or fewer carbon atoms is 18 to 50 by mass.

[0050]

[16] The polyamide resin composition according to any one of [1] to

[15] , wherein the weight-average molecular weight (Mw) of the aromatic vinyl copolymer (D) is 10,000 to 500,000.

[0051]

[17] The polyamide resin composition according to any one of [1] to

[16] further contains a flame retardant additive (F).

[0052]

[18] The polyamide resin composition according to any one of [1] to

[17] , wherein, relative to 100 parts by weight of the above-mentioned polyamide (A), it contains

[0053] 25-70 parts by weight of the above-mentioned brominated flame retardant (B)

[0054] 30 to 250 parts by weight of the above-mentioned inorganic filler material (C)

[0055] 0.1 to 10 parts by weight of the above-mentioned aromatic vinyl copolymer (D), and

[0056] 0.0005 to 20 parts by weight of the above colorant (E).

[0057] A method for manufacturing a polyamide resin composition as described in any one of

[19] [1] to

[18] , wherein the polyamide (A), the brominated flame retardant (B), the inorganic filler (C), the aromatic vinyl copolymer (D), the colorant (E), and a flame retardant additive (F) added as needed are melt-blended.

[0058]

[20] A molded body, which is a molded body of the polyamide resin composition described in any one of [1] to

[18] .

[0059]

[21] According to the molded body described in

[20] , it is a connector.

[0060]

[22] The molded body described in

[20] or

[21] is a vehicle-mounted connector.

[0061] Invention Effects

[0062] According to the present invention, a polyamide resin composition capable of producing a flame-retardant polyamide resin molded article with excellent foaming resistance even when exposed to high temperatures during a reflow soldering process, a method for manufacturing the polyamide resin composition, and a molded article of the polyamide resin composition can be provided. Attached Figure Description

[0063] Figure 1 This is a magnified view of a section in the thickness direction of test piece C.

[0064] Figure 2 This is a 3D view of test piece C.

[0065] Figure 3 This is a photograph of the SEM image of the analysis area of ​​the test piece in Example 3. Detailed Implementation

[0066] The following description is based on an example of an embodiment of the present invention (hereinafter sometimes referred to as "this embodiment"). However, the embodiments shown below are illustrative examples used to embody the technical concept of the present invention, and the present invention is not limited to the following description.

[0067] Furthermore, while preferred embodiments are shown in this specification, combinations of two or more preferred embodiments are also preferred. Regarding the numerical ranges, when several numerical ranges exist, their lower and upper limits can be selectively combined to form preferred embodiments.

[0068] In this specification, when a numerical range of "XX~YY" is specified, it means "above XX and below YY".

[0069] In addition, in this specification, "~ unit" (here, "~" means monomer) means "structural unit derived from ~", for example, "dicarboxylic acid unit" means "structural unit derived from dicarboxylic acid", and "diamine unit" means "structural unit derived from diamine".

[0070] <Polyamide Resin Composition>

[0071] One embodiment of the polyamide resin composition of the present invention contains polyamide (A) with a melting point of 280°C or higher, a brominated flame retardant (B), an inorganic filler (C), an aromatic vinyl copolymer (D), and a colorant (E).

[0072] The polyamide (A) described above contains diamine units, wherein 50 to 100 mol% of the diamine units are aliphatic diamine units having 4 to 18 carbon atoms.

[0073] The aforementioned colorant (E) is at least one of organic and inorganic colorants.

[0074] When observing the particles of the brominated flame retardant (B) in a region at a specific depth from the main surface of the test piece in the thickness direction section of the test piece containing the above-mentioned polyamide resin composition, the Rs1 (μm) shown in the above formula (1) is... 2 Less than 0.2μm 2 .

[0075] One embodiment of the polyamide resin composition of the present invention contains polyamide (A) with a melting point of 280°C or higher, a brominated flame retardant (B), an inorganic filler (C), an aromatic vinyl copolymer (D), and a colorant (E).

[0076] The polyamide (A) described above contains diamine units, wherein 50 to 100 mol% of the diamine units are aliphatic diamine units having 4 to 18 carbon atoms.

[0077] The aforementioned colorant (E) is at least one of organic and inorganic colorants.

[0078] When observing the particles of the brominated flame retardant (B) in the region at a specific depth from the main surface of the test piece in the thickness direction section of the test piece containing the above polyamide resin composition, the Rs2 (μm) shown in the above formula (2) is less than 1.7 μm.

[0079] One embodiment of the polyamide resin composition of the present invention contains polyamide (A) with a melting point of 280°C or higher, a brominated flame retardant (B), an inorganic filler (C), an aromatic vinyl copolymer (D), and a colorant (E).

[0080] The polyamide (A) described above contains diamine units, wherein 50 to 100 mol% of the diamine units are aliphatic diamine units having 4 to 18 carbon atoms.

[0081] The aforementioned colorant (E) is at least one of organic and inorganic colorants.

[0082] When observing a region at a specific depth from the main surface of a test piece containing the above-mentioned polyamide resin composition in the thickness direction cross-section, the number average cross-sectional area As (μm) of the particles of the above-mentioned brominated flame retardant (B) is... 2 Less than 0.1μm 2 .

[0083] One embodiment of the polyamide resin composition of the present invention contains polyamide (A) with a melting point of 280°C or higher, a brominated flame retardant (B), an inorganic filler (C), an aromatic vinyl copolymer (D), and a colorant (E).

[0084] The polyamide (A) described above contains diamine units, wherein 50 to 100 mol% of the diamine units are aliphatic diamine units having 4 to 18 carbon atoms.

[0085] The aforementioned colorant (E) is at least one of organic and inorganic colorants.

[0086] When observing a region at a specific depth from the main surface of a test piece containing the above-mentioned polyamide resin composition in the thickness direction section, the product of the average diameter EqD of a circle having the same area as the cross-sectional area of ​​the particles of the above-mentioned brominated flame retardant (B) and π, i.e., EqD×π (μm), is less than 1.0 μm.

[0087] The inventors have observed that the tendency for bubbling to occur when a flame-retardant polyamide resin molded article is exposed to high temperatures during a reflow soldering process is influenced by the particle morphology of the brominated flame retardant (B) in the flame-retardant polyamide resin molded article. Based on this observation, the present invention provides a polyamide resin composition capable of producing a flame-retardant polyamide resin molded article with excellent bubbling resistance.

[0088] Specifically, in one embodiment of the present invention, if the Rs1 in the test piece containing the polyamide resin composition is less than a specific value, a flame-retardant polyamide resin molded article exhibiting excellent foaming resistance even when exposed to high temperatures during the reflow soldering process can be obtained. Furthermore, in one embodiment of the present invention, if the Rs2 in the test piece containing the polyamide resin composition is less than a specific value, a flame-retardant polyamide resin molded article exhibiting excellent foaming resistance even when exposed to high temperatures during the reflow soldering process can be obtained. In one embodiment of the present invention, if both the Rs1 and Rs2 in the test piece containing the polyamide resin composition are less than the aforementioned specific value, a flame-retardant polyamide resin molded article exhibiting excellent foaming resistance even when exposed to high temperatures during the reflow soldering process can be obtained more reliably.

[0089] In one embodiment of the present invention, if the As content in the test piece containing the polyamide resin composition is less than a specific value, a flame-retardant polyamide resin molded article exhibiting excellent foaming resistance even when exposed to high temperatures during the reflow soldering process can be obtained. Furthermore, in one embodiment of the present invention, if the EqD×π content in the test piece containing the polyamide resin composition is less than a specific value, a flame-retardant polyamide resin molded article exhibiting excellent foaming resistance even when exposed to high temperatures during the reflow soldering process can be obtained. In one embodiment of the present invention, if both the As content and the EqD×π content in the test piece containing the polyamide resin composition are less than the aforementioned specific value, a flame-retardant polyamide resin molded article exhibiting excellent foaming resistance even when exposed to high temperatures during the reflow soldering process can be obtained more reliably.

[0090] In this invention, the reasons for believing that foaming can be suppressed are explained from the viewpoint of the form in which the brominated flame retardant (B) exists in the molded article. However, this invention is not limited to this explanation.

[0091] First, it is believed that blistering is caused by the internal pressure generated when moisture and gas contained in the molded body are exposed to high temperatures, causing vaporization and expansion. It is said that water vapor has difficulty permeating the brominated flame retardant (B). Therefore, in this invention, it is believed that when the moisture contained in the molded body becomes water vapor internally, if the particle size of the brominated flame retardant (B) in the molded body is small, it is easy to ensure a path for the water vapor to be released to the outside, thus suppressing blistering. Another cause of blistering is believed to be the weak interfacial adhesion between the polyamide (A) and the brominated flame retardant (B). Therefore, the brominated flame retardant (B) becomes coarse due to stretching and agglomeration during the molding process, for example, and thus becomes the starting point for minute interfacial damage when internal pressure is generated. In this case, it is believed that by sufficiently reducing the particle size of the brominated flame retardant (B) in the molded body, the agglomeration of the brominated flame retardant (B) can also be suppressed, thereby suppressing blistering.

[0092] The parameters Rs1 and Rs2 are explained.

[0093] Rs1 is represented by the following equation (1).

[0094] Rs1=(bs / as)×As (1)

[0095] In equation (1),

[0096] bs / as is the numerical average of the ratios of the vertical Ferrette diameters of the particles of brominated flame retardant (B) observed in the aforementioned region to the minimum Ferrette diameter, and...

[0097] As is the number average (μm) of the cross-sectional area of ​​brominated flame retardant (B) particles observed in the above region. 2 ).

[0098] It should be noted that "the perpendicular Ferete diameter relative to the minimum Ferete diameter" refers to the Ferete diameter that is perpendicular to the minimum Ferete diameter after measuring 10 Ferete diameters at 18° intervals within the range of 0 to 162°.

[0099] As shown in the above formula, Rs1 is a parameter containing information related to the cross-sectional area of ​​the brominated flame retardant (B) particles observed in the aforementioned region. There is a tendency to obtain molded articles with better foaming resistance when the value of Rs1 is smaller. Rs1 is preferably 0.15 μm. 2 The following is more preferably 0.1 μm 2 Below. The lower limit of Rs1 is greater than 0 μm. 2 The lower limit of Rs1 is preferably 0.01 μm. 2 The above, more preferably 0.03μm2 The above is further preferably 0.05μm. 2 The above. Rs1 can be obtained by performing image analysis on the SEM image using the methods described in the embodiments below.

[0100] Rs2 is represented by the following equation (2).

[0101] Rs2=(bs / as)×EqD×π (2)

[0102] In equation (2),

[0103] bs / as is the numerical average (μm) of the ratio of the vertical Ferrette diameter to the minimum Ferrette diameter of the Ferrette diameter of the particles of brominated flame retardant (B) observed in the above region, and...

[0104] EqD is the numerical average (μm) of the diameter of a perfect circle having the same area as the cross-sectional area of ​​the brominated flame retardant (B) particles observed in the aforementioned region.

[0105] As shown in the above formula, Rs2 is a parameter that includes EqD, which is the numerical average of the diameters of circles with the same area as the brominated flame retardant (B) observed in the aforementioned region. There is a tendency to obtain molded articles with better foaming resistance when the value of Rs2 is smaller. In one embodiment of the invention, Rs2 is preferably 1.6 μm or less, more preferably 1.5 μm or less, even more preferably 1.4 μm or less, even more preferably 1.2 μm or less, and even more preferably 1.1 μm or less. The lower limit of Rs2 is greater than 0 μm. The lower limit of Rs2 is not particularly limited, but for example, it is preferably 0.1 μm or more, more preferably 0.3 μm or more, even more preferably 0.5 μm or more, and even more preferably 0.7 μm or more. Rs2 can be calculated from a value obtained by image analysis of SEM images using the method described in the embodiments below.

[0106] In one embodiment of the present invention, Rs1 is preferably less than 0.2 μm. 2 Furthermore, Rs2 is less than 1.7 μm. More preferably, Rs1 is 0.15 μm. 2 Furthermore, Rs2 is 1.6 μm or less. More preferably, Rs1 is 0.1 μm. 2 The value is below 1.5 μm and Rs2 is below 1.5 μm.

[0107] The parameters As and EqD×π are explained.

[0108] As contains information related to the cross-sectional area of ​​the brominated flame retardant (B) particles, which is the number-average (μm) cross-sectional area of ​​the brominated flame retardant (B) particles observed in the above region. 2As can be obtained by performing image analysis on the SEM image using the methods described in the embodiments described later.

[0109] There is a tendency that a smaller As value results in a molded article with better foam resistance. In one embodiment of the present invention, As is preferably 0.075 μm. 2 Below, 0.06 μm is more preferred. 2 Hereinafter, 0.05 μm is further preferred. 2 The lower limit for As is greater than 0 μm. 2 Preferably 0.005μm 2 The above, more preferably 0.01μm 2 The above is further preferably 0.03μm. 2 above.

[0110] In EqD×π, EqD is the numerical average of the diameters of a circle having the same area as the cross-sectional area of ​​the brominated flame retardant (B) particles observed in the aforementioned region. EqD×π is a parameter containing information related to the circumference of a circle having the same area as the cross-sectional area of ​​the brominated flame retardant (B) particles observed in the aforementioned region. EqD can be obtained by image analysis of the SEM image using the methods described in the embodiments below.

[0111] There is a tendency that the smaller the value of EqD×π, the better the molded article's foam resistance. In one embodiment of the present invention, EqD×π is preferably 0.9 μm or less, more preferably 0.8 μm or less, and even more preferably 0.7 μm or less. The lower limit of EqD×π is greater than 0 μm. The lower limit of EqD×π is not particularly limited, but for example, it is preferably 0.1 μm or more, more preferably 0.2 μm or more, even more preferably 0.3 μm or more, and even more preferably 0.5 μm or more.

[0112] In one embodiment of the present invention, As is preferably less than 0.1 μm. 2 Furthermore, EqD×π is less than 1.0 μm. More preferably, As is 0.075 μm. 2 Furthermore, EqD×π is less than 1.0 μm. Preferably, As is 0.075 μm. 2 The following values ​​are below EqD×π and are below 0.8μm.

[0113] Test piece C, which contains a polyamide resin composition, is described. Figure 1 This is a partially enlarged view of a cross-section in the thickness direction of test piece C, which contains a polyamide resin composition. Figure 1In the diagram, the vertical direction represents the T-direction (thickness direction), and the horizontal direction represents the W-direction (width direction). Test piece C can be obtained by molding the polyamide resin composition or by cutting it from a molded polyamide resin composition. Figure 1 In this study, the upper surface of test piece C is designated as the principal surface. Furthermore, the position (distance) within test piece C in the T direction from this principal surface (0 μm) is defined as the depth. Figure 2 This is a perspective view of test piece C, which contains a polyamide resin composition. Figure 2 In addition to the T and W directions, the L direction (length direction) is also shown. From the perspective of uniform dimensions, test piece C is set to be 30mm in length × 10mm in width × 1.0mm in thickness. For the thickness direction section of test piece C, given that test piece C is 30mm in length × 10mm in width × 1.0mm in thickness, from the perspective of uniform cutting position, as follows... Figure 2 As shown, the preferred location is a surface 1.0 mm (=0.1 cm) away from one end of the test piece C in the L direction (length direction) and parallel to the width direction. When the test piece C is obtained by injection molding, the end of the test piece C in the length direction is more preferably the end on the upstream side (gate side) corresponding to the macroscopic resin flow direction during injection molding.

[0114] In this embodiment, a specific region is defined as a 25μm wide area within a cross-section of a test piece C containing a polyamide resin composition. This area has a length of 30mm, a width of 10mm, and a thickness of 1.0mm, a depth of 250μm ± 8.8μm from the main surface of the test piece C, and is orthogonal to the thickness direction of the test piece C. Figure 1The area enclosed by the dashed line (hereinafter also referred to as the "surface area"). It should be noted that 250μm±8.8μm refers to 241.2~258.8μm. From the viewpoint of uniformity, the midpoint of the width of this surface area orthogonal to the thickness direction of the test piece C is preferably the center of the width direction of the test piece C. That is, this surface area is preferably a region in the thickness direction cross-section of the test piece C containing the polyamide resin composition (30mm in length × 10mm in width × 1.0mm in thickness), with a depth of 250μm±8.8μm from the main surface of the test piece C, and a width of 25μm orthogonal to the thickness direction with the center of the width direction of the test piece C as its midpoint. Thus, information related to the cross-sectional area of ​​the brominated flame retardant (B) particles in the surface area of ​​the test piece can be obtained. It should be noted that the main surface of the test piece is the starting point of the depth. When the test piece C is obtained by injection molding, from the viewpoint of starting point in a uniform thickness direction, the surface located vertically above the macroscopic resin flow direction during injection molding (the so-called upper surface) is preferably used as the main surface. Furthermore, when the test piece C is cut from the molded body of the polyamide resin composition, it is preferable to cut it in a manner that includes the surface of the molded body, and use that surface as the main surface.

[0115] In the surface region, the smaller the particles of the brominated flame retardant (B), the more effectively it suppresses the tendency to generate foam. Therefore, in the resin composition of one embodiment of the present invention, the number average cross-sectional area As (μm) of the brominated flame retardant (B) particles observed in the surface region of the above formula (1) is... 2 Preferably less than 0.10 μm 2 More preferably 0.09μm 2 Hereinafter, 0.08μm is further preferred. 2 Hereinafter, 0.06μm is even more preferred. 2 Hereinafter, 0.05 μm is even more preferred. 2 As described above, the numerical average value of the cross-sectional area As can be obtained by image analysis of the SEM image using the method described in the embodiments below.

[0116] In the surface region, the smaller the particles of the brominated flame retardant (B), the more effectively it suppresses the tendency to generate foam. Therefore, in the resin composition of one embodiment of the present invention, the numerical average value EqD of the diameter of the perfect circle with the same area as the particles of the brominated flame retardant (B) observed in the surface region of the above formula (2) is preferably 0.40 μm or less, more preferably 0.35 μm or less, even more preferably 0.31 μm or less, and even more preferably 0.22 μm or less. As described above, the numerical average value EqD (μm) can be obtained in the form of an EqD value by performing image analysis on the SEM image using the method described in the examples described later.

[0117] In this embodiment, both Rs1 and Rs2 contain information related to the Ferrette diameter, specifically information related to (bs / as). This information related to the Ferrette diameter, specifically information related to (bs / as), can be obtained by image analysis of the SEM image using the methods described in the embodiments described later.

[0118] The Ferrette diameter typically refers to the distance between two parallel tangents along a specified orientation of a particle relative to the image analysis object (also simply referred to as the "object"). In image analysis, by setting the horizontal direction of the image to 0° and changing the angle at 18° intervals, the minimum Ferrette diameter can be determined from the obtained Ferrette diameters. In this embodiment, since the aforementioned path in the thickness direction section of the test piece is taken into account, the Ferrette diameter is a two-dimensional Ferrette diameter.

[0119] When observing the surface region of the aforementioned test piece C, a scanning electron microscope (SEM) is preferred, and a field emission scanning electron microscope (FE-SEM) is more preferred. Furthermore, image analysis of the obtained images is preferred, and the software used for image analysis is preferably "Avizo 3D" manufactured by Thermo Fisher Scientific.

[0120] The brominated flame retardant (B) is compounded with other components, and its average diameter typically decreases due to the application of shear based on melt mixing and shear based on injection molding. On the other hand, the brominated flame retardant (B) may agglomerate during cooling after injection molding or be affected by internal stresses (e.g., pressure in the resin flow direction and stress caused by changes in the alignment direction of the inorganic filler material (C), thereby causing the particles of the brominated flame retardant (B) to take on a shape extending along the direction of stress. Therefore, when observing a cross-section, the average value of the bs / as ratio of the brominated flame retardant (B) particles contained in the molded body of the polyamide resin composition of this embodiment tends to be greater than 1, specifically greater than 1.4. Furthermore, when observing a cross-section, the aforementioned As and EqD×π of the brominated flame retardant (B) particles contained in the molded body of the polyamide resin composition of this embodiment tend to be large.

[0121] However, even when the particle size of the brominated flame retardant (B) is 1.4 or higher in terms of bs / as, the likelihood of it significantly hindering the aforementioned path and becoming a minor starting point for destruction is low when the particle size is sufficiently small. Therefore, in one embodiment of the present invention, the cross-sectional area of ​​the brominated flame retardant (B) particles present in a specific region is represented by the above formula (1). The reason for multiplying bs / as by the cross-sectional area in formula (1) is that the more the flame retardant is stretched, the higher the probability of hindering gas diffusion and becoming a minor starting point for destruction. Similarly, in one embodiment of the present invention, the circumference of a circle having the same area as the cross-sectional area of ​​the brominated flame retardant (B) particles present in a specific region is set as EqD×π, represented by the above formula (2). The reason for multiplying bs / as by EqD×π in formula (2) is that the more the flame retardant is stretched, the higher the probability of hindering gas diffusion and becoming a minor starting point for destruction. Furthermore, the values ​​obtained from these formulas, namely Rs1 and Rs2, are smaller than the specific values ​​mentioned above, thereby solving the aforementioned problem.

[0122] Regarding this embodiment, even when the particles of the brominated flame retardant (B) take an extended shape, the possibility of significantly obstructing the aforementioned path and becoming minor points of failure is minimized when the particle size is sufficiently small. Therefore, in one embodiment of the present invention, As represents the cross-sectional area of ​​the brominated flame retardant (B) particles present in a specific region. Similarly, in one embodiment of the present invention, EqD×π represents the circumference of a circle having the same area as the cross-sectional area of ​​the brominated flame retardant (B) particles present in the specific region. Furthermore, by making these values ​​smaller than specific values, the aforementioned problems can be solved.

[0123] The components of the polyamide resin composition of this embodiment will be described below.

[0124] [Polyamide (A)]

[0125] The polyamide (A) used in this embodiment has a melting point of 280°C or higher and contains diamine units.

[0126] The aforementioned diamine unit comprises 50-100 mol% of aliphatic diamine units having 4-18 carbon atoms. By comprising 50-100 mol% of aliphatic diamine units having 4-18 carbon atoms in the diamine unit, it is possible to obtain a molded article with excellent foaming resistance even when exposed to high temperatures during the reflow soldering process. The content of aliphatic diamine units having 4-18 carbon atoms in the aforementioned diamine unit is preferably 75-100 mol%, more preferably 85-100 mol%.

[0127] Polyamide (A) can be one type or two or more types.

[0128] Examples of aliphatic diamines with 4 to 18 carbon atoms that constitute the aliphatic diamine unit include straight-chain aliphatic diamines such as 1,4-butanediamine, 1,5-pentanediamine, 1,6-hexanediamine, 1,7-heptanediamine, 1,8-octanediamine, 1,9-nonanediamine, 1,10-decanediamine, 1,11-undecanediamine, and 1,12-dodecanediamine; and 1-butyl-1,2-ethylenediamine, 1,1-dimethyl-1,4-butanediamine, and 1-ethyl-1,4-butanediamine. Diamine, 1,2-dimethyl-1,4-butanediamine, 1,3-dimethyl-1,4-butanediamine, 1,4-dimethyl-1,4-butanediamine, 2,3-dimethyl-1,4-butanediamine, 2-methyl-1,5-pentanediamine, 3-methyl-1,5-pentanediamine, 2,5-dimethyl-1,6-hexanediamine, 2,4-dimethyl-1,6-hexanediamine, 3,3-dimethyl-1,6-hexanediamine, 2,2-dimethyl-1,6-hexanediamine, 2,2,4- Trimethyl-1,6-hexanediamine, 2,4,4-trimethyl-1,6-hexanediamine, 2-propyl-1,6-hexanediamine, 2,4-diethyl-1,6-hexanediamine, 2,2-dimethyl-1,7-heptanediamine, 2,3-dimethyl-1,7-heptanediamine, 2,4-dimethyl-1,7-heptanediamine, 2,5-dimethyl-1,7-heptanediamine, 2-ethyl-1,7-heptanediamine, 2-methyl-1,8-octanediamine, 3-methyl-1,8-octanediamine, 4 Branched aliphatic diamines such as 1,3-dimethyl-1,8-octanediamine, 1,4-dimethyl-1,8-octanediamine, 2,4-dimethyl-1,8-octanediamine, 3,4-dimethyl-1,8-octanediamine, 4,5-dimethyl-1,8-octanediamine, 2,2-dimethyl-1,8-octanediamine, 3,3-dimethyl-1,8-octanediamine, 4,4-dimethyl-1,8-octanediamine, and 5-methyl-1,9-nonanediamine. From the viewpoint of excellent physical properties such as heat resistance and low water absorption, the preferred material is at least one selected from 1,4-butanediamine, 1,6-hexanediamine, 1,9-nonanediamine, 2-methyl-1,8-octanediamine, and 1,10-decanediamine; more preferably, at least one selected from 1,9-nonanediamine, 2-methyl-1,8-octanediamine, and 1,10-decanediamine; even more preferably, at least one selected from 1,9-nonanediamine and 2-methyl-1,8-octanediamine; and even more preferably, a combination of 1,9-nonanediamine and 2-methyl-1,8-octanediamine.

[0129] As an aliphatic diamine with 4 to 18 carbon atoms, when 1,9-nonanediamine and 2-methyl-1,8-octanediamine are used together, from the viewpoint of heat resistance, the molar ratio of 1,9-nonanediamine to 2-methyl-1,8-octanediamine (1,9-nonanediamine / 2-methyl-1,8-octanediamine) is preferably in the range of 95 / 5 to 40 / 60, more preferably in the range of 90 / 10 to 50 / 50, and even more preferably in the range of 90 / 10 to 60 / 40.

[0130] Polyamide (A) may contain diamine units other than aliphatic diamine units having 4 to 18 carbon atoms. Examples of diamines constituting these other diamine units include aliphatic diamines with 2 or 3 carbon atoms, aromatic diamines, and alicyclic diamines. Examples of aliphatic diamines with 2 or 3 carbon atoms include ethylenediamine, 1,2-propanediamine, and 1,3-propanediamine. Examples of aromatic diamines include p-phenylenediamine, m-phenylenediamine, p-phenylenediamine, m-phenylenediamine, 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenyl sulfone, and 4,4'-diaminodiphenyl ether. Examples of alicyclic diamines include cyclohexanediamine, methylcyclohexanediamine, isophoronediamine, norbornenedimethylamine, and tricyclodecanedimethylamine.

[0131] These diamines can be used alone or in combination with two or more.

[0132] Without impairing the effects of the present invention, the polyamide (A) may further contain structural units derived from polyamines of 3 or more members, such as bis(hexamethylene)triamine, within the range that it can be melt-formed.

[0133] When the polyamide (A) contains other diamine units, the content of such units in the total number of diamine units constituting the polyamide (A) is preferably 50 mol% or less, more preferably 30 mol% or less, even more preferably 20 mol% or less, and even more preferably 10 mol% or less.

[0134] Polyamide (A) contains any dicarboxylic acid unit.

[0135] Examples of dicarboxylic acids that constitute dicarboxylic acid units include malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, octanoic acid, azelaic acid, sebacic acid, undecanoic acid, dodecanoic acid, dimethylmalonic acid, 2,2-diethylsuccinic acid, 2,2-dimethylglutaric acid, 2-methyl adipic acid, trimethyl adipic acid, and other aliphatic dicarboxylic acids; 1,3-cyclopentanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, and cycloheptanedicarboxylic acid. Formic acid, cyclooctanedicarboxylic acid, cyclodecanedicarboxylic acid, and other alicyclic dicarboxylic acids; terephthalic acid, isophthalic acid, phthalic acid, 2,6-naphthalenedicarboxylic acid, 2,7-naphthalenedicarboxylic acid, 1,4-naphthalenedicarboxylic acid, 1,4-phenylenedioxydiacetic acid, 1,3-phenylenedioxydiacetic acid, biphenyl dicarboxylic acid, diphenylmethane-4,4'-dicarboxylic acid, diphenylsulfone-4,4'-dicarboxylic acid, 4,4'-biphenyl dicarboxylic acid, and other aromatic dicarboxylic acids. These dicarboxylic acids can be used alone or in combination of two or more.

[0136] Without impairing the effects of the invention, the polyamide (A) may contain structural units derived from polycarboxylic acids. Examples of structural units derived from polycarboxylic acids include trimellitic acid, pyromellitic acid, and pyromellitic tetroxide. Preferably, it contains units within a range suitable for melt forming.

[0137] The dicarboxylic acid unit preferably contains 50 mol% or more, more preferably 60 mol% or more, and even more preferably 75 mol% or more of terephthalic acid units, and can be 100 mol%. By including 50 mol% or more of terephthalic acid units in the dicarboxylic acid unit, it is possible to obtain a molded article with superior foaming resistance even when exposed to high temperatures during the reflow soldering process. In one embodiment, the polyamide (A) contains dicarboxylic acid units, wherein 50 mol% or more of the dicarboxylic acid units are terephthalic acid units, and the aliphatic diamines constituting the 4-18 carbon aliphatic diamine units are at least one selected from 1,4-butanediamine, 1,6-hexanediamine, 1,9-nonanediamine, 2-methyl-1,8-octanediamine, and 1,10-decanediamine.

[0138] From the viewpoint of increasing the degree of polymerization, the molar ratio of dicarboxylic acid units to diamine units in polyamide (A) [dicarboxylic acid unit / diamine unit] is preferably 45 / 55 to 55 / 45, more preferably 47 / 53 to 53 / 47.

[0139] It should be noted that the molar ratio of dicarboxylic acid units to diamine units can be adjusted according to the molar ratio of the dicarboxylic acid and diamine in the raw material.

[0140] The total content of dicarboxylic acid units and diamine units in 100 mol% of polyamide (A) is preferably 80 mol% or more, more preferably 90 mol% or more, further preferably 95 mol% or more, and even more preferably 99 mol% or more, and can be 100 mol%.

[0141] The polyamide (A) preferably has at least 10% of its terminal groups on its molecular chain capped by a capping agent. More preferably, the proportion of terminal groups on the molecular chain capped by the capping agent (capping rate) is at least 20%.

[0142] As capping agents, monofunctional compounds that react with the amino or carboxyl groups at the ends of the polyamide can be used. From the viewpoints of reactivity and capping stability, monocarboxylic acids or monoamines are preferred, and monocarboxylic acids are more preferred from the viewpoints of ease of handling. In addition, monoisocyanates, monoacyl halides, monoesters, and monoalcohols can also be used as capping agents.

[0143] As a capping agent, monocarboxylic acids that react with amino groups can be used, such as aliphatic monocarboxylic acids like acetic acid, propionic acid, butyric acid, valeric acid, hexanoic acid, octanoic acid, lauric acid, tridecanoic acid, myristic acid, palmitic acid, stearic acid, tervaric acid, and isobutyric acid; alicyclic monocarboxylic acids like cyclohexanecarboxylic acid; aromatic monocarboxylic acids like benzoic acid, toluic acid, α-naphthoic acid, β-naphthoic acid, methylnaphthoic acid, and phenylacetic acid; and any mixture thereof. Among these, acetic acid, propionic acid, butyric acid, valeric acid, hexanoic acid, octanoic acid, lauric acid, tridecanoic acid, myristic acid, palmitic acid, stearic acid, and benzoic acid are preferred from the perspectives of reactivity, capping stability, and price.

[0144] As monoamines used as end-capping agents, monoamines reactive to carboxyl groups can be used, such as aliphatic monoamines like methylamine, ethylamine, propylamine, butylamine, hexylamine, octylamine, decylamine, stearylamine, dimethylamine, diethylamine, dipropylamine, and dibutylamine; alicyclic monoamines like cyclohexylamine and dicyclohexylamine; aromatic monoamines like aniline, toluidine, diphenylamine, and naphthylamine; and any mixtures thereof. Among these, butylamine, hexylamine, octylamine, decylamine, stearylamine, cyclohexylamine, and aniline are preferred from the perspectives of reactivity, boiling point, end-capping stability, and price.

[0145] The end-capping ratio of polyamide (A) is determined by measuring the number of carboxyl-terminal groups, amino-terminal groups, and end groups capped by the end-capping agent present in polyamide (A), according to the following formula (I). From the viewpoint of accuracy and simplicity, the number of each end group is preferably determined by... 1 H-NMR is obtained by integrating the characteristic signals corresponding to each terminal group.

[0146] End capping rate (%) = [(TS) / T] × 100 (I)

[0147] [In the formula, T represents the total number of terminal groups in the molecular chain of polyamide (A) (which is usually equal to twice the number of polyamide molecules), and S represents the total number of uncapped carboxyl and amino terminals remaining.]

[0148] Polyamide (A) can be manufactured using any method known as a method for manufacturing crystalline polyamide. For example, it can be manufactured by solution polymerization or interfacial polymerization using diamine and dicarboxylic acid in the form of acyl chloride as raw materials, melt polymerization using dicarboxylic acid and diamine as raw materials, solid-state polymerization, melt extrusion polymerization, etc.

[0149] In addition to its heat resistance, from the perspective of maximizing the effects of the present invention, the melting point of polyamide (A) is 280°C or higher, preferably 290°C or higher, and more preferably 300°C or higher. Furthermore, from the viewpoint of suppressing the thermal decomposition of polyamide during melt molding, it is preferably 350°C or lower, more preferably 340°C or lower, and even more preferably 330°C or lower.

[0150] It should be noted that when using two or more polyamides, the melting point of polyamide (A) being 280°C or higher means that the melting point is calculated as a weighted average of the melting points of each polyamide and the content (mass%) of each polyamide relative to 100% of the total polyamides.

[0151] The melting point of polyamide (A) can be determined using differential scanning calorimetry (DSC) as the peak temperature of the endothermic peak that appears when the temperature is increased at a rate of 10 °C / min.

[0152] From the viewpoint of heat resistance, the glass transition temperature of polyamide (A) is preferably 100°C or higher, more preferably 110°C or higher, and even more preferably 120°C or higher. There is no particular upper limit to the glass transition temperature of polyamide (A), but from the viewpoint of processability, it is preferably 180°C or lower, more preferably 160°C or lower, and can be 150°C or lower. In other words, the glass transition temperature of polyamide (A) is preferably 100–180°C, more preferably 110–160°C, and even more preferably 120–150°C.

[0153] The glass transition temperature of polyamide (A) can be determined using differential scanning calorimetry (DSC) as the temperature at which the inflection point occurs when the temperature is increased at a rate of 20 °C / min.

[0154] From the viewpoint of leveraging the mechanical properties and heat resistance of polyamide, the content (mass%) of polyamide (A) in the total amount of polyamide resin composition of this embodiment is preferably 20 to 70% by mass, more preferably 25 to 70% by mass, even more preferably 30 to 65% by mass, and even more preferably 30 to 50% by mass.

[0155] [Brominated flame retardant (B)]

[0156] The polyamide resin composition of this embodiment contains a brominated flame retardant (B). By containing a brominated flame retardant (B), the polyamide resin composition achieves improved flame retardancy.

[0157] Examples of brominated flame retardants (B) used in this embodiment include hexabromocyclododecane, decabromodiphenyl ether, octabromodiphenyl ether, tetrabromobisphenol A, bis(tribromophenoxy)ethane, bis(pentabromophenoxy)ethane, tetrabromobisphenol A epoxy resin, tetrabromobisphenol A carbonate, ethylene(bistetrabromophthalic acid)imide, ethylenebispentabromobiphenyl, tris(tribromophenoxy)triazine, bis(dibromopropyl)tetrabromobisphenol A, bis(dibromopropyl)tetrabromobisphenol S, brominated polyphenylene ethers such as poly(di)bromophenyl ether, polydibromostyrene, polytribromostyrene, brominated polystyrene, polybromostyrene, brominated crosslinked aromatic polymers, brominated epoxy resins, brominated phenoxy resins, brominated styrene-maleic anhydride polymers, tetrabromobisphenol S, tris(tribromoneopentyl) phosphate, polybrominated trimethylphenylindane, tris(dibromopropyl)-isocyanurate, etc.

[0158] Furthermore, examples of the aforementioned brominated polystyrene include uncrosslinked and unmodified brominated polystyrene, crosslinked brominated polystyrene, and modified brominated polystyrene with added functional groups. Examples of functional groups include epoxy groups such as glycidyl methacrylate, and anhydride groups containing α,β-unsaturated dicarboxylic acid anhydrides such as maleic anhydride and citrate anhydride. The modification rate is preferably 0.1 to 20% by mass, more preferably 0.5 to 10% by mass. Similarly, examples of the aforementioned polybrominated polystyrene include unmodified polybrominated polystyrene and modified polybrominated polystyrene with added functional groups. The functional groups and modification rates in the modified polybrominated polystyrene are the same as those described above for the modified brominated polystyrene.

[0159] These brominated flame retardants (B) can be used alone or in combination of two or more. The brominated flame retardant (B) preferably comprises at least one selected from the group consisting of brominated polystyrene and polybrominated polystyrene, more preferably comprising one selected from the group consisting of brominated polystyrene and one selected from the group consisting of polybrominated polystyrene, and even more preferably comprising modified brominated polystyrene with added functional groups and one selected from the group consisting of polybrominated polystyrene.

[0160] Brominated polystyrene can be manufactured, for example, by polymerizing styrene monomers to produce polystyrene, followed by brominating the benzene rings of the polystyrene. Polybrominated polystyrene can also be manufactured by polymerizing brominated styrene monomers (bromostyrene, dibromostyrene, tribromostyrene, etc.).

[0161] The bromine content in both brominated polystyrene and polybrominated polystyrene is preferably 55-75% by mass, more preferably 55-70% by mass. By setting the bromine content to 55% by mass or more, the amount of bromine required for flame retardancy can be met with a small amount of both brominated polystyrene and polybrominated polystyrene. In addition, the reduction in mechanical properties can be suppressed, and molded articles with excellent mechanical properties and heat resistance can be obtained. Furthermore, by setting the bromine content to 75% by mass or less, thermal decomposition is less likely to occur during melt processing such as extrusion and molding, gas generation can be suppressed, and molded articles with excellent heat resistance and colorfastness can be obtained.

[0162] From the viewpoint of obtaining a molded article with excellent flame retardancy, the content (mass%) of brominated flame retardant (B) in the total amount of the polyamide resin composition of this embodiment is preferably 10 to 40% by mass, more preferably 12 to 35% by mass, and even more preferably 15 to 30% by mass.

[0163] The content of brominated flame retardant (B) relative to 100 parts by weight of polyamide (A) is preferably 25 to 70 parts by weight, more preferably 30 to 65 parts by weight, and even more preferably 35 to 60 parts by weight. If the content of brominated flame retardant (B) is 25 parts by weight or more, a molded article with excellent flame retardancy can be obtained. Furthermore, if the content of brominated flame retardant (B) is 70 parts by weight or less, a molded article with better foaming resistance, flame retardancy, and mechanical properties, even when exposed to high temperatures during the reflow soldering process, can be obtained. When using multiple brominated flame retardants (B), their total amount should be within the above-mentioned range.

[0164] [Inorganic filler material (C)]

[0165] The polyamide resin composition of this embodiment contains an inorganic filler (C). Examples of inorganic fillers (C) include carbon nanotubes, fullerenes, talc, wollastonite, zeolite, sericite, mica, kaolin, clay, pyrophyllite, silica, bentonite, aluminum silicate, silicon dioxide, magnesium oxide, aluminum oxide, magnesium carbonate, dolomite, calcium sulfate, calcium hydroxide, magnesium hydroxide, ground fibers, glass powder, ceramic beads, boron nitride, silicon carbide, halloysite, vermiculite, and various other clay minerals and glass fibers. These inorganic fillers (C) can be used individually or in combination of two or more.

[0166] From the viewpoint of improving the mechanical properties of the molded polyamide resin composition, the inorganic filler material (C) preferably contains glass fiber or wollastonite, more preferably glass fiber (C1), and even more preferably glass fiber (C1).

[0167] The glass fiber (C1) is preferably the glass fiber described below. The average fiber length of the glass fiber (C1) is preferably 1 to 10 mm, more preferably 1 to 7 mm, and even more preferably 2 to 4 mm.

[0168] From the viewpoint of obtaining molded articles with superior foam resistance and mechanical properties, the average fiber diameter of the glass fiber (C1) is preferably 6 to 20 μm, more preferably 6 to 15 μm. It should be noted that while it is known that glass fibers (C1) with a small average fiber diameter exhibit good foam resistance, in this invention, even glass fibers (C1) with a larger average fiber diameter can be used. Therefore, the average fiber diameter of the glass fiber (C1) is further preferably 9 to 13 μm, and even more preferably 10 to 12 μm.

[0169] The average fiber length and average fiber diameter of glass fiber (C1) can be obtained as follows: by using image analysis of an electron microscope, the fiber length and fiber diameter of 400 randomly selected glass fibers (C1) are measured, and their average values ​​are calculated.

[0170] In addition, the average fiber length and average fiber diameter of the glass fibers (C1) in the polyamide resin composition or the molded body can be determined, for example, by dissolving the polyamide resin composition or the molded body in an organic solvent, extracting the glass fibers (C1), and determining them by image analysis using an electron microscope, as described above.

[0171] Examples of cross-sectional shapes for glass fiber (C1) include circular, rectangular, oblong (nearly rectangular), elliptical, cocoon-shaped, and cocoon-shaped with a central portion contracting along the length. Among these, the cross-sectional shape of glass fiber (C1) is preferably circular, rectangular, oblong (nearly rectangular), elliptical, or cocoon-shaped, and more preferably circular.

[0172] The glass fiber (C1) may contain at least one surface treatment agent selected from coupling agents and slugging agents. For example, the glass fiber (C1) may contain a slugging agent. Alternatively, the glass fiber (C1) may contain both a coupling agent and a slugging agent. The glass fiber (C1) preferably contains a surface treatment agent on its surface. The amount of surface treatment agent attached relative to the total mass of the glass fiber (C1) (i.e., the combined mass of the glass fiber (C1) and the surface treatment agent) is generally preferably 0.01% by mass or more. From the viewpoint of foam resistance, it is preferably 0.01% by mass or more and 2.0% by mass or less, more preferably 0.2% by mass or more and 0.9% by mass or less, and even more preferably 0.3% by mass or more and 0.5% by mass or less.

[0173] Examples of coupling agents include silane coupling agents and titanium coupling agents. Examples of silane coupling agents include γ-methacryloyloxypropyltrimethoxysilane, γ-epoxypropoxypropyltrimethoxysilane, and γ-aminopropyltriethoxysilane.

[0174] Examples of bridging agents include urethane resin-based bridging agents, acrylic resin-based bridging agents, epoxy resin-based bridging agents, and resin-based bridging agents containing anhydride groups. However, when urethane resin-based bridging agents, acrylic resin-based bridging agents, and epoxy resin-based bridging agents contain anhydride groups, they are classified as resin-based bridging agents containing anhydride groups. Resin-based bridging agents containing anhydride groups are composed of resins containing at least anhydride groups, preferably copolymers containing anhydride groups. From the viewpoint of obtaining molded articles with better foaming resistance and better mechanical properties, the bridging agent preferably includes at least one selected from epoxy resin-based bridging agents and resin-based bridging agents containing anhydride groups. From the viewpoint of obtaining molded articles with better foaming resistance, the bridging agent preferably includes epoxy resin-based bridging agents. From the viewpoint of obtaining molded articles with better flowability, the bridging agent preferably includes urethane resin-based bridging agents. It is believed that selecting appropriate surface treatment agents for glass fiber (C1) helps to impart strength to the molded body that can withstand the internal pressure of water vapor even under the peak temperature conditions of the reflow soldering process.

[0175] The content of inorganic filler (C) relative to 100 parts by weight of polyamide (A) is preferably 30 to 250 parts by weight, more preferably 35 to 200 parts by weight, further preferably 40 to 150 parts by weight, and even more preferably 45 to 100 parts by weight. If the content of inorganic filler (C) is 30 parts by weight or more, a molded article with better mechanical properties can be obtained; if it is 250 parts by weight or less, shear heating during melt mixing can be suppressed.

[0176] [Aromatic vinyl copolymer (D)]

[0177] From the viewpoint of obtaining a flame-retardant polyamide resin molded article with excellent foaming resistance, the polyamide resin composition of this embodiment contains an aromatic vinyl copolymer (D) (hereinafter also referred to as "copolymer (D)"). Therefore, it is possible to maintain Rs1 as shown in formula (1) above at less than 0.2 μm. 2 The value of . Furthermore, it is possible to maintain Rs2 as shown in equation (2) above at a value less than 1.7 μm. In one embodiment of the present invention, it is possible to make As less than 0.1 μm. 2 Furthermore, in one embodiment of the present invention, the aforementioned EqD×π can be made less than 1.0 μm. This can be understood from the comparison between the examples exemplified in the Example section and the comparative examples. One of the main reasons why the copolymer (D) brings about such an effect is that the copolymer (D) improves the compatibility between the components in the polyamide resin composition, thereby suppressing the aggregation of brominated flame retardant (B) particles that are prone to form during cooling.

[0178] From the viewpoints of flame retardancy, heat resistance and formability, the copolymer (D) preferably contains structural units derived from at least one of styrene and α-methylstyrene, and structural units derived from at least one of maleic anhydride and monoalkyl maleic anhydride having 1 to 3 carbon atoms, more preferably containing structural units derived from styrene and structural units derived from maleic anhydride.

[0179] From the viewpoints of flame retardancy, heat resistance and formability, the content of structural units in the copolymer (D) derived from at least one of maleic anhydride and monoalkyl maleic anhydride having 1 to 3 carbon atoms is preferably 3 to 50% by mass, more preferably 5 to 50% by mass, further preferably 18 to 50% by mass, and even more preferably 18 to 45% by mass.

[0180] The copolymer (D) may further have structural units other than those derived from at least one structural unit selected from styrene and α-methylstyrene, and structural units derived from at least one structural unit selected from maleic anhydride and monoalkyl maleic anhydride having 1 to 3 carbon atoms. The total content of the structural units derived from at least one structural unit selected from styrene and α-methylstyrene, and structural units derived from at least one structural unit selected from maleic anhydride and monoalkyl maleic anhydride having 1 or more carbon atoms and less than 3 carbon atoms in the copolymer (D) is preferably 80% by mass or more, more preferably 90% by mass or more, and even more preferably 100% by mass.

[0181] The glass transition temperature of the copolymer (D) is preferably 120°C or higher, more preferably 120–200°C, even more preferably 125–180°C, and even more preferably 125–160°C. If the glass transition temperature of the copolymer (D) is 120°C or higher, the flame retardancy and heat resistance can be further improved; if it is 200°C or lower, the thermal decomposition of polyamide during melt molding can be suppressed.

[0182] The glass transition temperature of copolymer (D) can be determined using differential scanning calorimetry (DSC) as the temperature at which the inflection point occurs when the temperature is increased at a rate of 20 °C / min.

[0183] From the viewpoint of flame retardancy and heat resistance, the weight-average molecular weight (Mw) of the copolymer (D) is preferably 10,000 to 500,000, more preferably 20,000 to 400,000, even more preferably 30,000 to 300,000, and even more preferably 50,000 to 200,000.

[0184] The weight-average molecular weight (Mw) of the copolymer (D) was determined by gel permeation chromatography (GPC) in polystyrene form.

[0185] From the viewpoint of imparting compatibility with polyamide (A), the acid value of copolymer (D) is preferably 200–400 mg KOH / g, more preferably 250–350 mg KOH / g. The acid value can be determined by near-infrared spectroscopy or by a neutralization test using potassium hydroxide.

[0186] The copolymer (D) can be a commercially available product or a copolymer synthesized by known methods. In addition, the bonding morphology of the structural unit derived from at least one of styrene and α-methylstyrene and the structural unit derived from at least one of maleic anhydride and monoalkyl maleic anhydride having 1 or more and 3 or fewer carbon atoms is not particularly limited, and can be any form of random polymerization, block polymerization, or graft polymerization.

[0187] From the viewpoint of obtaining a flame-retardant polyamide resin molded article with excellent foaming resistance, the content of copolymer (D) relative to 100 parts by mass of polyamide (A) is preferably 0.1 to 10 parts by mass, more preferably 0.5 to 8 parts by mass, further preferably 0.8 to 5 parts by mass, even more preferably 1.0 to 4 parts by mass, and most preferably 1.2 to 3 parts by mass.

[0188] [Coloring agent (E)]

[0189] The polyamide resin composition of this embodiment imparts visibility and decorative properties by containing a colorant (E).

[0190] The colorant (E) used in this embodiment is at least one of organic and inorganic colorants. The colorant (E) can be used alone or in combination with two or more types.

[0191] Examples of organic colorants include anthraquinone dyes, violet ketone dyes, anthraquinone dyes, methine dyes, azazine dyes, azo dyes, azomethyl base dyes, phthalocyanine dyes, quinone imine dyes, quinoline dyes, nitro dyes, indigo dyes, and oxazine dyes; azo lake pigments, insoluble monoazo pigments, insoluble diazo pigments, and chelated azo pigments; and phthalocyanine pigments, perylene pigments, violet ketone pigments, anthraquinone pigments, quinacridone pigments, dioxazine pigments, thioindolinone pigments, isoindolineone pigments, quinophthalone pigments, diketopyrrolopyrrole pigments, benzimidazolone pigments, and vat pigments.

[0192] From the viewpoints of heat resistance, color development, and compatibility, the dyes are preferably selected from at least one of anthraquinone dyes, violet ketone dyes, anthraquinone dyes, phthalocyanine dyes, azo pigments, and phthalocyanine pigments; more preferably, they are selected from at least one of anthraquinone dyes, violet ketone dyes, anthraquinone dyes, and phthalocyanine dyes. Similarly, from the same viewpoint, quinoline dyes, anthraquinone dyes, violet ketone dyes, anthraquinone dyes, phthalocyanine dyes, azo pigments, and phthalocyanine pigments are preferred; more preferably, they are selected from at least one of quinoline dyes, anthraquinone dyes, violet ketone dyes, and phthalocyanine pigments.

[0193] As inorganic colorants, examples include black inorganic pigments such as carbon black, lampblack, acetylene black, bone black, thermal cracking carbon black, channel black, furnace black, and titanium black; metal oxides such as titanium oxide (TiO, Ti2O3, TiO2), zinc oxide (Pb3O4), iron oxide (Fe2O3), antimony oxide, and zirconium oxide; metal sulfides such as zinc sulfide; ultramarine (Pigment Blue 29); zinc phosphate; barium sulfate; manganese phosphate; cobalt aluminate; cobalt stannate; cobalt zincate; antimony oxide; antimony sulfide; cerium sulfide; lanthanum sulfide; chromium oxide; zinc chromate; and composite metal oxides containing various oxides such as nickel-based, bismuth-based, vanadium-based, molybdenum-based, cadmium-based, titanium-based, zinc-based, manganese-based, cobalt-based, iron-based, chromium-based, antimony-based, magnesium-based, and aluminum-based oxides.

[0194] From the viewpoint of heat resistance, it is preferable to use at least one selected from black inorganic pigments, metal oxides, metal sulfides, and composite metal oxides, and more preferably at least one selected from carbon black, metal oxides, metal sulfides, and composite metal oxides. From the viewpoint of providing a molded article other than black, it is preferable to use at least one selected from metal oxides, metal sulfides, and composite metal oxides.

[0195] When the colorant (E) contains an organic colorant, from the viewpoint of flame retardancy, color development and mechanical properties, the content of the organic colorant is preferably 0.0001 to 0.5% by mass relative to 100% by mass of the polyamide resin composition of this embodiment, more preferably 0.001 to 0.5% by mass, and even more preferably 0.005 to 0.5% by mass.

[0196] When the colorant (E) contains an inorganic colorant, from the viewpoint of flame retardancy, color development and mechanical properties, the content of the inorganic colorant is preferably 0.001 to 5.0% by mass relative to 100% by mass of the polyamide resin composition of this embodiment, more preferably 0.01 to 5.0% by mass, and even more preferably 0.1 to 5.0% by mass.

[0197] The content of colorant (E) relative to 100 parts by weight of polyamide (A) is preferably 0.0005 to 20 parts by weight, more preferably 0.001 to 15 parts by weight, even more preferably 0.01 to 10 parts by weight, even more preferably 0.1 to 5 parts by weight, and even more preferably 0.2 to 1 part by weight. If the content of colorant (E) is 0.0005 parts by weight or more, a color with high visibility can be developed; if it is 20 parts by weight or less, the reduction of mechanical properties of the molded article can be suppressed.

[0198] From the viewpoint of meeting the specifications required for automotive parts and electrical / electronic parts applications, the polyamide resin composition of this embodiment preferably has a ΔE greater than 1, as shown in the following formula (3). From the viewpoint of improving visibility, ΔE is more preferably greater than 3, further preferably greater than 10, and even more preferably greater than 30.

[0199] The inorganic filler (C) and colorant (E) contained in the polyamide resin composition of this embodiment are preferably selected to satisfy this requirement.

[0200] [Mathematical Expression 2]

[0201] ... (X)

[0202] In equation (X), ΔE is derived from CIE1976 (L * a * b * The color difference specified in the color system.

[0203] L * col a * col and b * colThe polyamide resin composition of this embodiment is derived from CIE1976 (L * a * b * The color system specified by L * a * and b * That is, the polyamide resin composition of this embodiment is conformed to CIE1976 (L... * a * b * The color system specified by L * For L * col a * For a * col b * For b * col .

[0204] L * nat a * nat and b * nat It is a polyamide resin composition without colorant that has the same composition as the above-mentioned polyamide resin composition except that it does not contain colorant (E), as specified in CIE1976 (L). * a * b * The color system specified by L * a * and b * That is, a polyamide resin composition without colorant that has the same composition as the above-described polyamide resin composition except that it does not contain colorant (E), as specified in CIE 1976 (L). * a * b * The color system specified by L * For L * nat a * For a * nat b * For b * nat .

[0205] The aforementioned ΔE can be determined by the following method. Prepare the polyamide resin composition of this embodiment and a colorless polyamide resin composition with the same composition as the polyamide resin composition of this embodiment except that it does not contain colorant (E). Prepare dumbbell-shaped tensile test pieces (type A1) of each resin composition using the method according to JIS K7139:2009. Obtain images of each test piece using a colorimeter, and obtain the L value of each test piece based on these images.* a * b * ΔE can be calculated. More specifically, it can be calculated using the method described in the embodiments described later.

[0206] [Flame retardant additive (F)]

[0207] The polyamide resin composition of this embodiment may further contain a flame retardant additive (F). By using the flame retardant additive (F) in combination with a brominated flame retardant (B), the resulting molded article exhibits even better flame retardancy.

[0208] Examples of flame retardant additives (F) include antimony compounds such as antimony oxides (antimony trioxide, antimony tetroxide, antimony pentoxide, etc.) and antimonates such as sodium antimonate; melamine compounds such as melamine orthophosphate, melamine pyrophosphate, melamine borate, and melamine polyphosphate; tin oxides such as tin monoxide and tin dioxide; iron oxides such as iron oxide and γ-iron oxide; metal oxides such as manganese oxide, molybdenum oxide, cobalt oxide, bismuth oxide, tin oxide, nickel oxide, copper oxide, and tungsten oxide; metal hydroxides such as aluminum hydroxide; metal powders such as aluminum, iron, titanium, manganese, zinc, molybdenum, cobalt, bismuth, chromium, tin, antimony, nickel, copper, and tungsten; metal carbonates such as zinc carbonate and barium carbonate; metal borates such as zinc borate and calcium borate; zinc stannate such as zinc tin trioxide; and organosilicon. However, substances belonging to inorganic fillers (C) and colorants (E) are excluded. They can be used individually or in combination of two or more.

[0209] Of the above, preferably, it is selected from at least one of antimony compounds, melamine compounds, metal oxides, metal hydroxides, metal borates and zinc stannate, more preferably from at least one of antimony trioxide, antimony tetroxide, antimony pentoxide, sodium antimonate, melamine orthophosphate, melamine pyrophosphate, melamine borate, melamine polyphosphate, aluminum hydroxide, zinc borate and zinc tin trioxide.

[0210] The flame retardant additive (F) is preferably contained in the polyamide resin composition of this embodiment in powder form. The upper limit of its average particle size is preferably 30 μm, more preferably 15 μm, further preferably 10 μm, and particularly preferably 7 μm. On the other hand, the lower limit of the average particle size of the flame retardant additive (F) is preferably 0.01 μm. When the average particle size is between 0.01 and 30 μm, the flame retardancy of the resulting molded article is improved.

[0211] It should be noted that in this specification, "average particle size" refers to the volume average particle size, which can be calculated based on the particle size distribution that accounts for 50% of the cumulative volume (50% particle size D50) measured using a laser diffraction particle size distribution measuring device.

[0212] When the polyamide resin composition of this embodiment contains a flame retardant (F), the content of the flame retardant (F) relative to 100 parts by weight of polyamide (A) is preferably 1 to 20 parts by weight, more preferably 2 to 18 parts by weight, further preferably 3 to 15 parts by weight, and even more preferably 4 to 10 parts by weight. This significantly achieves the aforementioned effects.

[0213] [Other ingredients]

[0214] In addition to the polyamide (A), brominated flame retardant (B), inorganic filler (C), aromatic vinyl copolymer (D), colorant (E), and flame retardant additive (F) used as needed, the polyamide resin composition of this embodiment may also contain other components as needed.

[0215] Other components include, for example, stabilizers such as copper compounds; antioxidants such as hindered phenolic antioxidants, hindered amine antioxidants, phosphorus antioxidants, and sulfur antioxidants; ultraviolet absorbers; light stabilizers; antistatic agents; heat stabilizers; crystallizing nucleating agents; plasticizers; lubricants; release agents; slip agents; dispersants; oxygen absorbers; hydrogen sulfide adsorbents; crystallization delay agents; impact modifiers such as α-olefin copolymers and rubbers; and anti-drip agents such as fluoropolymers.

[0216] The content of the other components mentioned above is not particularly limited as long as it does not impair the effect of the present invention. The content is preferably 0.02 to 200 parts by weight relative to 100 parts by weight of polyamide (A), more preferably 0.03 to 100 parts by weight, further preferably 0.05 to 50 parts by weight, and even more preferably 0.1 to 20 parts by weight.

[0217] In this embodiment, the total content of polyamide (A), brominated flame retardant (B), inorganic filler (C), aromatic vinyl copolymer (D), and colorant (E) in the polyamide resin composition is preferably 70% by mass or more, more preferably 80% by mass or more, further preferably 85% by mass or more, and even more preferably 90% by mass or more.

[0218] In the polyamide resin composition of this embodiment, it is preferable that, relative to 100 parts by weight of the polyamide (A), there are 25 to 70 parts by weight of the brominated flame retardant (B), 30 to 250 parts by weight of the inorganic filler (C), 0.1 to 10 parts by weight of the aromatic vinyl copolymer (D), and 0.0005 to 20 parts by weight of the colorant (E).

[0219] (Method for manufacturing polyamide resin composition)

[0220] There are no particular limitations on the method of manufacturing the polyamide resin composition, and known methods can be used. For example, a method can be described by melt-blending polyamide (A), brominated flame retardant (B), inorganic filler (C), aromatic vinyl copolymer (D), colorant (E), and flame retardant additive (F) as needed, along with other components mentioned above.

[0221] There are no particular limitations on the melt blending method, and methods that can uniformly mix the above components are preferred. For example, single-screw extruders, twin-screw extruders, kneaders, Banbury mixers, etc. are preferred. The melt blending conditions are not particularly limited as long as they can sufficiently reduce the particle size of the brominated flame retardant (B). For example, a method of melt blending for about 1 to 30 minutes in a temperature range that is about 10 to 50°C higher than the melting point of polyamide (A) can be cited.

[0222] <Molded body>

[0223] By forming the above-described polyamide resin composition into, for example, granules and supplying them to various molding methods, molded articles can be obtained. The molding method can be appropriately selected according to the application, and methods such as injection molding, extrusion molding, blow molding, compression molding, pressing molding, and calendering can be employed. In the case of manufacturing components such as connectors, injection molding is preferred. The molded article of the polyamide resin composition in this embodiment is preferably an injection-molded article.

[0224] In particular, the polyamide resin composition of this embodiment provides a flame-retardant polyamide resin molded body with excellent foaming resistance even when exposed to high temperatures during the reflow soldering process, and therefore the molded body is suitable as an injection molded body for use in applications with surface mount processes (hereinafter also referred to as "SMT processes").

[0225] Injection molding can be performed using a commercially available injection molding machine. Injection molding can be performed, for example, with an injection speed of 60 mm / s, a holding pressure of 60 MPa, a holding time of 1.0 second, a cooling time of 4.0 seconds, and a cycle time of 11.0 seconds. Although this also depends on the composition, the injection time is approximately 0.15 seconds, and the filling pressure is approximately 60 MPa. The barrel temperature can be set, for example, sequentially from the barrel nozzle to 320°C, 320°C, 320°C, 320°C, and 300°C. Preferably, by performing injection molding in this way, a molded body with Rs1 satisfying a specific range can be obtained. Similarly, a molded body with Rs2 satisfying a specific range can be obtained. Similarly, a molded body with As satisfying a specific range can be obtained. Similarly, a molded body with EqD×π satisfying a specific range can be obtained.

[0226] <Uses>

[0227] The polyamide resin composition of this embodiment can be used as various molded articles of any shape and purpose, such as electrical components, electronic components, automotive components, industrial components, faucet components, fibers, films, sheets, household goods, leisure goods, etc.

[0228] As electrical and electronic components, examples include connectors such as FPC connectors, B2B connectors, card connectors, SMT connectors (coaxial connectors, etc.), and memory card connectors; SMT relays; SMT wire winding tubes; slots such as memory slots and CPU slots; switches such as command switches and SMT switches; optical components such as fiber optic components and optical sensors; LED components such as LED reflectors; and electronic substrates such as solar cell substrates, LED mounting substrates, flexible printed circuit boards, and resin-molded circuit boards.

[0229] As automotive components, examples include: thermostat housings, coolant control valve housings, thermal management module housings, radiator cans, radiator hoses, water outlets, water inlets, water pump housings, and rear connectors; intercooler cans, intercooler housings, turbine ducts, EGR cooler housings, resonators, throttle bodies, intake manifolds, and tailpipes; fuel system components such as fuel delivery pipes, fuel tanks, quick connectors, canisters, pump modules, fuel lines, oil filters, lock nuts, and sealing materials; structural components such as mounting brackets, torsion bars, and cylinder head covers; and bearing retainers, gear lockers, headlight actuator gears, and throttle bodies. Drive system components such as door gears, sliding door rollers, and clutch peripheral parts; braking system components such as air brake pipes; vehicle electrical components such as wiring harness connectors, motor components, sensors, ABS spools, combination switches, and vehicle switches in the engine compartment; and interior and exterior components such as sliding door dampers, door and rearview mirror brackets, door and rearview mirror holders, roof rails, engine mounting brackets, air filter intake pipes, door limiters, plastic chains, vehicle emblems, clips, circuit breaker covers, cup holders, airbags, mudguards, spoilers, radiator brackets, radiator grilles, louvers, air scrapers, engine hoods, rear doors, and fuel sensor modules.

[0230] As industrial components, examples include gas pipelines, oilfield development pipes, hoses, termite-proof cables (communication cables, route cables, etc.), coating parts for powder coatings (inner coatings for water pipes, etc.), subsea oilfield pipes, pressure hoses, hydraulic pipes, coating pipes, fuel pump housings and impellers, separators, booster pipes, butterfly valves, conveyor roller bearings, railway sleeper spring seats, outboard motor engine covers, generator engine covers, wind turbine blades, irrigation valves, large switches, and monofilaments (extruded yarns) for fishing nets, etc.

[0231] Examples of faucet components include: housings for water supply components, housings for water storage components, housings for filter housings, faucet housings, pipe housings, bathroom faucet housings (hot water switching valves, flow switching valves, etc.), sanitary component housings, kitchen faucet housings, water heater housings, valve components (stop ball, slide valve, cylinder) and valve component housings, toilet stop valve housings, shower head housings, water heater valve housings, connectors for residential piping (underfloor piping, etc.), bathroom faucet connectors, water supply pipe connectors, and pipes. Connectors, water meter housings, water meter components (bearings, propellers, pins) and water meter, gas meter housings, distributor housings, valve / pump housings for household appliances, steam-resistant components for steam irons, internal containers for electric kettles, dishwasher components (washing tub, washing nozzles, baskets), pump housings, pump components (e.g., turbines, impellers), housings for water supply systems (warm water tanks, etc.), housings for heating systems, housings for refrigeration systems, water flow regulating valves, pressure reducing valves, overflow valves, solenoid valves, three-way valves, thermostatic valves, hot water temperature sensors, water flow sensors, bathtub adapters, etc.

[0232] Examples of household appliances include valve / pump housings for tea and coffee makers; valve / pump housings for cooking appliances such as rice cookers and steamers; steam-resistant components for cooking appliances such as rice cookers and steamers (e.g., the lid of a rice cooker); sliding components for cooking appliances such as rice cookers and steamers (e.g., gears); sliding components for professional cooking appliances (e.g., gears for gear pumps); and steam-resistant components for professional cooking appliances (e.g., pipes in a professional rice cooker).

[0233] Examples of leisure products include the insoles of athletic shoes, racket frames and grommets, golf club heads and sleeves, fishing reels and rods, boat screws, bicycle suspensions, gears, saddles, bottle cages, etc.

[0234] The polyamide resin composition of this embodiment can be manufactured by injection molding, thus making it suitable for electrical and electronic components that require the manufacture of multiple parts in a short time. Specifically, it is suitable for electrical and electronic components that include SMT processes, and more specifically, it is suitable for surface mount components such as connectors supporting SMT, SMT relays, SMT wire guides, sockets, command switches, SMT switches, camera modules, power supply components, sensors, capacitor banks, hard disk components, resistors, fuse holders, coil holders, IC housings, etc.

[0235] A particularly suitable example of the molded body of the polyamide resin composition of this embodiment is a part of an automotive connector supporting SMT (Surface Mount Technology). SMT-compatible automotive connectors typically have a housing and terminals made of a resin composition using a resin with a melting point of 260°C or higher. SMT-compatible automotive connectors may include sealing rings, gaskets, and housings. Automotive connectors are generally larger in size than connectors for consumer electronics. Furthermore, during the SMT process, they are exposed to higher temperatures, making it difficult for moisture inside the molded body to evaporate during the preheating process, thus easily leading to blistering. High flame retardancy is also required. Moreover, due to the stringent quality requirements for automotive applications, blistering is not permissible. Therefore, the molded body must exhibit excellent blistering resistance even when exposed to high temperatures during the SMT process. The molded body of the polyamide resin composition of this embodiment meets these requirements and is therefore suitable as a part of an automotive connector.

[0236] Example

[0237] The present invention will now be described in detail through examples and comparative examples, but the present invention is not limited to these examples and comparative examples.

[0238] The evaluations in the examples and comparative examples were performed according to the methods shown below.

[0239] <1. Color Value (ΔE)>

[0240] The color value (L) of the polyamide resin compositions obtained in each embodiment and comparative example * a * b * The determination was performed under the following apparatus and conditions. For the determination, based on the polyamide resin compositions obtained in the examples and comparative examples, test piece A was prepared using the method according to JIS K7139:2009. col Dumbbell-shaped tensile test pieces (Type A1) were prepared. Furthermore, compared to the polyamide resin compositions obtained in the various examples and comparative examples, a polyamide resin composition with the same composition was prepared except that it did not contain colorant (E), and dumbbell-shaped tensile test pieces (Type A1) were similarly prepared (test piece A). nat ).

[0241] Regarding the measurement, the following measuring apparatus, light source, sensor, and measuring geometry are used to acquire an image, which is then sent to the following application device. The following software is used on the following application device to obtain L. * a * b * .

[0242] Measuring apparatus: RAL gGmbH colorimeter, RAL COLORCATCH NANO

[0243] Light source: CIE standard light source D65

[0244] Sensor: CCD camera (224×224 pixels)

[0245] Determine geometry: 45° / 0°

[0246] Software: RAL iCOLOURS (version 3.7.2)

[0247] Device used: Apple iPhone 8 (iOS 13.3) (registered trademark)

[0248] Based on the obtained L * a * b * Calculate ΔE as shown in the following equation (X).

[0249] [Mathematical Expression 3]

[0250] ... (X)

[0251] It should be noted that in equation (X), L * col a * col and b * col The polyamide resin compositions obtained in each example (test piece A) col ) by CIE1976 (L * a * b * The color system specified by L * a * and b * L * nat a * nat and b * nat A colorless polyamide resin composition (test piece A) with the same composition as the above-mentioned polyamide resin composition except that it does not contain colorant (E). nat ) by CIE1976 (L * a * b * The color system specified by L * a * and b * ΔE is shown in Table 1.

[0252] <2. Evaluation of flame retardancy>

[0253] Flame retardancy is evaluated in accordance with the UL-94 standard.

[0254] Using an injection molding machine manufactured by Nissei Resin Kogyo Co., Ltd. (clamping force: 80 tons, screw diameter: φ26 mm), the polyamide resin composition obtained in the examples and comparative examples was used to form the polyamide resin composition at a barrel temperature (320°C) 14°C higher than the melting point of the polyamide in component (A) and a mold temperature of 140°C, resulting in multiple test pieces B1 with a thickness of 0.75 mm, a width of 13 mm, and a length of 125 mm. Similarly, multiple test pieces B2 with a thickness of 3.0 mm, a width of 13 mm, and a length of 125 mm were obtained.

[0255] Next, for the obtained test pieces B1 and B2, the upper ends were clamped with fixtures to fix each test piece vertically. A blue, specified flame with a height of 20±1mm was brought into contact with the lower end for 10 seconds and then removed. The burning time of each test piece was measured (first time). After extinguishing the flame, it was immediately brought into contact with the lower end again and separated, and the burning time of each test piece was measured (second time). The same measurement was repeated for 5 pieces, obtaining 5 data points for the burning time in the first time and 5 data points for the burning time in the second time, for a total of 10 data points. The sum of the 10 data points was set as T, and the maximum value among the 10 data points was set as M. Evaluation was carried out according to the following evaluation criteria.

[0256] Additionally, visually inspect for any dripping from the flame.

[0257] [Evaluation Criteria]

[0258] V-0: T is less than 50 seconds and M is less than 10 seconds, the material did not burn to the clamp, and even if molten material with flames fell, the cotton 12 inches below did not ignite.

[0259] V-1: When T is less than 250 seconds and M is less than 30 seconds, the molten material did not burn to the clamp, and even when molten material with flames fell, the cotton 12 inches below did not ignite.

[0260] V-2: When T is less than 250 seconds and M is less than 30 seconds, the molten material with flames falls and the cotton 12 inches below catches fire.

[0261] X: Cases that do not meet any of the evaluation criteria in UL94 above.

[0262] <3. Calculation of parameters Rs1, Rs2, As, EqD, and (bs / as)>

[0263] 3-1. Preparation of test piece C

[0264] Using an injection molding machine manufactured by Sumitomo Heavy Industries, Ltd. (clamping force: 18 tons, screw diameter: φ18 mm), the polyamide resin composition obtained in the examples and comparative examples was used. Under the conditions of a barrel temperature (320°C) 14°C higher than the melting point of the polyamide as component (A) and a mold temperature of 140°C, the polyamide resin composition was injection molded using a mold with a 10 mm wide and 0.9 mm high. Multiple sheet-shaped test pieces C containing the polyamide resin composition with a length of 30 mm × width of 10 mm × thickness of 1.0 mm were produced.

[0265] Injection molding was performed with an injection speed of 60 mm / s, a holding pressure of 60 MPa, a holding time of 1.0 second, a cooling time of 4.0 seconds, and a cycle time of 11.0 seconds. The results, while also depending on the composition, showed an injection time of approximately 0.15 seconds and a filling pressure of approximately 60 MPa. Regarding the barrel temperature settings, they were sequentially set to 320℃, 320℃, 320℃, 320℃, and 300℃, starting from the nozzle.

[0266] 3-2. Cross-sectional observation of test piece C

[0267] Relative to the resin flow direction during injection molding, the upper surface of the resulting test piece C is used as the main surface. The test piece C is then cut with a razor to create a cut surface, exposing the thickness-direction section (coronal plane) (see reference). Figure 1 The cutting position of test piece C is located 0.1 cm (=1 mm) away from the aforementioned film gate (one end of test piece C in the L direction), which serves as the starting point of the resin flow direction during injection molding, along the length direction (L direction) of test piece C, and is parallel to the width direction (W direction) of test piece C. Figure 2 (The single-dot dashed line). Next, the test piece C, whose cross-section in the thickness direction was exposed, was temporarily embedded in epoxy resin. Then, the cut surface of the test piece C was ground using a SERVTEC SP-150 mechanical grinder to finish the surface. Thus, test piece C with a ground surface was prepared.

[0268] Next, using a Hitachi High-Tech field emission scanning electron microscope "Regulus 8220" (detector: LA reflected electron mode), a reflected electron image (SEM image) of the polished surface of test piece C was obtained at 5000x magnification under high vacuum and at 23°C. The brightness and contrast of the image were then adjusted using the automatic brightness / contrast adjustment button.

[0269] 3-3. Image Analysis of Test Piece C

[0270] Next, based on the obtained SEM images, the SEM image of a region with a depth of 250 μm ± 8.8 μm from the main surface of test piece C and a width of 25 μm orthogonal to the thickness direction (T direction) was used as the analysis area. The width of this analysis area was defined as ± 12.5 μm from the center position (midpoint) in the width direction (W direction) of test piece C (refer to...). Figure 1 ).exist Figure 1 In a partially enlarged view of the thickness-direction section of test piece C, the analytical region is represented by the dashed line enclosed by the designated "region". Figure 3 The image shows an SEM image of the analytical area of ​​test piece C from Example 3. However, the brominated flame retardant in Comparative Example 4 had a large particle size and did not fall completely within the field of view, therefore it was determined that it could not be measured.

[0271] The SEM images of the analyzed area were imported into Avizo 3D (ver. 2022.2) image analysis software manufactured by Thermo Fisher Scientific (hereinafter referred to as the "analysis software") for image analysis. The images were acquired with the top edge of the SEM image parallel to the main surface of test piece C as the top edge of the acquired image. The SEM images of the analyzed area were converted to 0.02 μm / voxel data according to the following steps.

[0272] (1) Noise removal

[0273] The GPU Standard Mode was processed using the "Non-Local Means Filter" of the aforementioned analysis software. This removed noise from the image.

[0274] (2) Distinguish

[0275] In the images obtained in (1) above, the particles of polyamide (A), brominated flame retardant (B), and flame retardant additive (F) were binarized based on differences in brightness values, and labels were set. Except for Comparative Example 4, the images of the Examples and Comparative Examples do not contain inorganic filler material (C). Regarding the intensity range, polyamide (A) was 0 to 100, brominated flame retardant (B) was 93 to 165, and flame retardant additive (F) was 157 to 255. Furthermore, each value was set in a non-repeating manner for analysis.

[0276] Next, the "Marker-Based Watershed" function of the aforementioned analysis software was used. As a result, the particles of polyamide (A), brominated flame retardant (B), and flame retardant additive (F) were distinguished in a recognizable manner on the image.

[0277] (3) Divide the painting

[0278] In the image obtained in (2) above, the "Separate Objects" function of the analysis software is used for the particles of brominated flame retardant (B). Thus, a boundary line is set between adjacent particles of brominated flame retardant (B), and both are treated as individually identifiable particles.

[0279] Next, noise removal is performed. This removes dots and holes smaller than 10 pixels. It should be noted that dots and holes refer to an example of noise caused by reflection and scattering during the acquisition of SEM images.

[0280] (4) Analysis of the object

[0281] Next, for the image obtained in (3) above, the particles of the brominated flame retardant (B) are used as the object, and the following image analysis is performed using the functions of the analysis software described above.

[0282] (4-1)As

[0283] To determine As(μm) 2 Using the "Label Analysis" function of the aforementioned analysis software, proceed as follows.

[0284] Using the "Area" function within the "Label Analysis" feature, the cross-sectional area (μm²) of each particle of the brominated flame retardant (B) was obtained. 2 The values ​​of these are taken as the average of the number of objects, denoted as As(μm). 2 ).

[0285] (4-2) Calculation of Rs1 in Equation (1)

[0286] (4-2-1) In equation (1), bs / as

[0287] Use the "FeretShape" function within the "Label Analysis" feature of the aforementioned analysis software. Regarding the angle, set the horizontal angle of the image to 0°, and adjust the angle every 18°.

[0288] Thus, the FeretShape values ​​associated with each particle of the brominated flame retardant (B) are obtained. Then, the numerical average of these values ​​with respect to the number of objects is taken as the value of bs / as in equation (1).

[0289] (4-2-2) Calculation of Rs1

[0290] Rs1(μm) is calculated based on the following equation (1). 2 ).

[0291] Rs1=(bs / as)×As (1)

[0292] In this calculation, the As(μm) obtained in (4-1) above is used. 2 ) and the bs / as value obtained in (4-2-1) above.

[0293] (4-3) Calculation of EqD and EqD×π

[0294] To determine EqD (μm), the "Label Analysis" function of the aforementioned analysis software is used as follows.

[0295] Use the "EqDiameter" function within the "Label Analysis" framework. This yields the diameter of a circle with the same area as the cross-sectional area of ​​each particle of the brominated flame retardant (B). Then, the numerical average of these values ​​with respect to the number of objects is taken as the value of EqD (μm). Next, EqD × π is calculated.

[0296] Calculation of Rs2 in equation (2) (4-4)

[0297] Rs2(μm) is calculated based on the following equation (2).

[0298] Rs2=(bs / as)×EqD×π (2)

[0299] In this calculation, the EqD (μm) obtained in (4-3) above and the bs / as value obtained in (4-2-1) above are used.

[0300] <4. Evaluation of foaming resistance>

[0301] The test piece C obtained in step 3-1 above was left to stand for 168 hours at 85°C and 85% relative humidity. Then, these test pieces C were subjected to a reflow soldering test using a reflow soldering system (TAMURA Corporation, TNX25-30EM). During the reflow soldering test, the temperature was increased from 25°C to 150°C in 60 seconds, then to 180°C in 90 seconds, and further increased to the peak temperature in 60 seconds, held at the peak temperature for 20 seconds. The peak temperature was set to 270°C.

[0302] After the reflow soldering test, visually inspect the appearance of each test piece. If even one point of expansion occurs on the surface of test piece C, it is determined that blistering has occurred in test piece C.

[0303] The foaming rate was calculated based on the observations of 100 test pieces C. Specifically, the foaming rate was calculated as the percentage of test pieces that produced foaming even in one location out of 100 test pieces.

[0304] The following five levels of indicators are used to evaluate foaming resistance. If the evaluation result is "A" or "B", it means that there are no practical problems.

[0305] A: The foaming rate is above 0% and less than 10%.

[0306] B: Foaming rate is 10% or more but less than 25%.

[0307] C: Foaming rate is above 25% and less than 50%.

[0308] D: Foaming rate is above 50% and less than 75%.

[0309] E: Foaming rate is above 75% and below 100%.

[0310] <5. Evaluation of Bar-flow length>

[0311] Using an injection molding machine manufactured by Nissei Resin Kogyo Co., Ltd. (clamping force: 80 tons, screw diameter: φ26 mm), the polyamide resin composition obtained in the examples and comparative examples was used. Under the conditions of a barrel temperature (320°C) 14°C higher than the melting point of the polyamide of component (A), a mold with a width of 40 mm and a thickness of 0.5 mm, and a mold temperature of 140°C, the polyamide resin composition was injection molded 5 times at 1000 kgf, then 10 times at 750 kgf, and then 5 times at 750 kgf. The flow length (mm) of the resulting polyamide molded body was measured, and the average value was taken as the bar-flow length.

[0312] <6. Evaluation of Mechanical Properties>

[0313] The test piece is prepared as shown below. This test piece is then used to evaluate mechanical properties such as tensile and bending properties.

[0314] 6-1. Preparation of test pieces D and E

[0315] Using an injection molding machine manufactured by Sumitomo Heavy Industries, Ltd. (clamping force: 100 tons, screw diameter: φ32 mm), the polyamide resin composition obtained in the examples and comparative examples was used. Under the conditions of a barrel temperature (320°C) 14°C higher than the melting point of the polyamide of component (A) and a mold temperature of 140°C, the polyamide resin composition was molded using a T-runner mold to produce a multi-purpose test piece type A1 (dumbbell-shaped test piece as described in JIS K7139:2009: thickness 4 mm, total length 170 mm, parallel part length 80 mm, and central parallel part width 10 mm) (hereinafter also referred to as "test piece D").

[0316] In addition, a test piece (hereinafter also referred to as "test piece E") was formed with the same shape as test piece D and with a weld seam formed at the center of its parallel portion in a direction perpendicular to the length direction of the parallel portion.

[0317] 6-2. Tensile properties: tensile breaking strength and tensile failure strain

[0318] Using the test piece D prepared in 6-1 above, the tensile breaking strength (MPa) and tensile failure strain (%) were determined using a universal testing machine (Instron) at a test speed of 1 mm / min and a fixture spacing of 115 mm, in accordance with ISO 527-1 (2nd edition, 2012).

[0319] 6-3. Tensile properties: Welded tensile breaking strength

[0320] Using the test piece E prepared in 6-1 above, the weld tensile breaking strength (MPa) was determined using a universal testing machine (Instron) at a test speed of 1 mm / min and a fixture spacing of 115 mm, in accordance with ISO 527-1 (2nd edition, 2012).

[0321] 6-4. Bending properties: bending strength and flexural modulus

[0322] Using the test piece D prepared in 6-1 above, the flexural strength (MPa) and flexural modulus (GPa) were determined using a universal testing machine (Instron) at a test speed of 2 mm / min and a distance of 64 mm between support points, in accordance with ISO 178 (2nd edition, 2012).

[0323] <Example 1>

[0324] The following components are supplied from the uppermost hopper of a twin-screw extruder (STEER Engineering's "MEGA 32L": screw φ31.6mm, L / D=52, speed 150rpm, ejection rate 10kg / h): 100 parts by mass of polyamide (A2) as component (A), 49 parts by mass of granules of brominated flame retardant (B-1) as component (B), 1.2 parts by mass of aromatic vinyl copolymer (D-1) as component (D), 0.5 parts by mass of carbon black (E-1) as component (E), 7.1 parts by mass of flame retardant additive (F-1) as component (F), and other components such as antioxidant 0.5 parts by mass, anti-drip agent 1.2 parts by mass and mold release agent 0.7 parts by mass. In addition, 78 parts by mass of glass fiber (C1-2) as component (C) is supplied from the side feeder, and the mixture is melt-blended at 320°C.

[0325] The melt-blended polyamide resin composition was extruded into bundles, cooled, and then cut to obtain granules of the polyamide resin composition.

[0326] Using the obtained granules, test pieces of the specified shape were prepared according to the method described above, and various physical properties were evaluated. The results are shown in Table 1.

[0327] <Examples 2-9 and Comparative Examples 1-9>

[0328] The components were changed to the types and proportions listed in Tables 1 and 2, and melt-blended in the same manner as in Example 1 to obtain granules of the polyamide resin compositions of each example and comparative example. Furthermore, using the obtained granules, test pieces of a specified shape were produced by injection molding according to the method described above, and various physical properties were evaluated. The results are shown in Tables 1 and 2.

[0329] It should be noted that the components shown in Tables 1 and 2 are described below.

[0330] [Polyamide (A)]

[0331] • Polyamide (A-1): A polyamide with dicarboxylic acid units of terephthalic acid and diamine units of 1,9-nonanediamine and 2-methyl-1,8-octanediamine (molar ratio 85 / 15), melting point: 306℃, glass transition temperature: 125℃, intrinsic viscosity [η]: 0.80 dl / g

[0332] • Polyamide (A-2): A polyamide with dicarboxylic acid units of terephthalic acid and diamine units of 1,9-nonanediamine and 2-methyl-1,8-octanediamine (molar ratio 85 / 15). Melting point: 306℃, glass transition temperature: 125℃, intrinsic viscosity [η]: 0.93 dl / g

[0333] • Polyamide (A-3): A polyamide with dicarboxylic acid units of terephthalic acid and diamine units of 1,9-nonanediamine and 2-methyl-1,8-octanediamine (molar ratio 85 / 15). Melting point: 306℃, glass transition temperature: 125℃, intrinsic viscosity [η]: 1.0 dl / g

[0334] [Brominated flame retardant (B)]

[0335] • Flame retardant (B-1): Manufactured by LANXESS, trade name "Firemaster CP-44HF" (glycidyl methacrylate modified polybrominated styrene).

[0336] • Flame retardant (B-2): Manufactured by Albemarle, trade name "SAYTEX HP-7010" (brominated polystyrene).

[0337] • Flame retardant (B-3): Manufactured by LANXESS, trade name "PDBS-80" (brominated polystyrene).

[0338] [Inorganic filler material (C)]

[0339] • Glass fiber (C1-1): Manufactured by Central Glass Fiber Co., Ltd., trade name "ECS03-615" (Cross-section shape: round, average fiber diameter: 9μm, average cut fiber length: 3mm, amount of bundle binder (surface treatment agent) attached: 0.2% by mass relative to the total mass of glass fiber (C1))

[0340] • Glass fiber (C1-2): Manufactured by Nippon Electric Glass Co., Ltd., trade name "T-262H" (Cross-section shape: circular, average fiber diameter: 10.5μm, average fiber length: 3mm, amount of sizing agent (surface treatment agent) attached: 0.4% by mass relative to the total mass of glass fiber (C1))

[0341] [Aromatic vinyl copolymer (D)]

[0342] • Aromatic vinyl copolymer (D-1): Manufactured by Polyscope, trade name "XIBOND 160" (styrene-maleic anhydride copolymer, acid value: 250 mg KOH / g, glass transition temperature: 150℃, weight average molecular weight (Mw): 115,000)

[0343] • Aromatic vinyl copolymer (D-2): Manufactured by Polyscope, trade name "XIBOND 250" (styrene-maleic anhydride copolymer, acid value: 280 mg KOH / g, glass transition temperature: 130℃, weight average molecular weight (Mw): 10,000)

[0344] [Coloring agent (E)]

[0345] • Colorant (E-1): Carbon black manufactured by Mitsubishi Chemical Co., Ltd., trade name "#980B"

[0346] • Colorant (E-2): "Zinc sulfide" (white inorganic colorant, CAS No. 1314-98-3)

[0347] • Colorant (E-3): "Iron and manganese composite oxide" (red inorganic colorant, CAS No. 12062-81-6)

[0348] • Colorant (E-4): "Solvent Red 52" (Red organic colorant, quinoline dye, CAS No. 81-39-0)

[0349] • Colorant (E-5): “Pigment Blue 15” (Blue organic colorant, phthalocyanine pigment, CAS No. 147-14-8)

[0350] • Colorant (E-6): "Solvent Orange63" (Orange organic colorant, anthraquinone dye, CAS No. 16924-75-0)

[0351] • Colorant (E-7): "Solvent Red179" (Red organic colorant, violet ketone pigment, CAS No. 6829-22-7)

[0352] [Flame retardant additive (F)]

[0353] • Flame retardant additive (F-1): Manufactured by Japan Light Metals Co., Ltd., trade name "Flamtard S" (zinc stannate).

[0354] [Other ingredients]

[0355] • Antioxidant: Manufactured by Sumitomo Chemical Co., Ltd., trade name "Sumilizer GA-80" (3,9-bis{1,1-dimethyl-2-[β-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionyloxy]ethyl}-2,4,8,10-tetraoxaspiro[5.5]undecane)

[0356] • Anti-drip agent: Manufactured by Du Pont-Mitsui Fluorochemicals Co., Ltd., trade name "640-J" (polytetrafluoroethylene powder)

[0357] • Release agent: Manufactured by Mitsui Chemicals, Ltd., trade name "Hi-WAX 200P" (polyolefin wax).

[0358] [Table 1]

[0359]

[0360] [Table 2]

[0361]

[0362] As shown in Table 1, the polyamide resin compositions obtained in Examples 1 to 9 can all produce flame-retardant polyamide resin molded articles with excellent foaming resistance even when exposed to high temperatures during the reflow soldering process.

[0363] In Table 2, none of the polyamide resin compositions obtained in Comparative Examples 1-9 could produce flame-retardant polyamide resin molded articles with excellent foaming resistance even when exposed to high temperatures during the reflow soldering process. Regarding Comparative Examples 1-9, the reason for their poor foaming resistance can be attributed to the fact that Rs1 shown in Formula (1) exhibits a thickness of 0.2 μm. 2 The above values, and the Rs2 shown in Equation (2), show a large value of over 1.7 μm. Therefore, it can be seen that in order to provide a flame-retardant polyamide resin molded body with excellent foaming resistance even when exposed to high temperatures during the reflow soldering process, for the polyamide composition prepared by melt mixing, test pieces were made by injection molding to confirm that the Rs1 shown in Equation (1) is less than 0.2 μm. 2 As shown in equation (2), Rs2 should be less than 1.7 μm.

[0364] Furthermore, in Table 2, none of the polyamide resin compositions obtained in Comparative Examples 1-9 exhibited excellent foaming resistance even when exposed to high temperatures during the reflow soldering process. Regarding Comparative Examples 1-9, the reason for their poor foaming resistance can be attributed to the As content exhibiting a thickness of 0.1 μm. 2 The above values, EqD×π, show large values ​​above 1.0 μm. Therefore, to provide flame-retardant polyamide resin molded parts with excellent foaming resistance even when exposed to high temperatures during reflow soldering, test pieces were made by injection molding of polyamide compositions prepared by melt mixing, confirming that As is less than 0.1 μm. 2 EqD×π must be less than 1.0μm.

[0365] Industrial availability

[0366] The molded articles of the polyamide resin composition of the present invention are useful for various molded articles that require high reliability of electrical connection, especially automotive parts and electrical and electronic parts.

Claims

1. A polyamide resin composition containing a polyamide (A) having a melting point of 280°C or higher, a bromine-based flame retardant (B), an inorganic filler (C), an aromatic vinyl-based copolymer (D), and a colorant (E), the polyamide (A) contains diamine units, 50 to 100 mole% of the diamine units being aliphatic diamine units having a carbon number of 4 to 18, the colorant (E) is at least one of an organic colorant and an inorganic colorant, When the particles of the bromine-based flame retardant (B) in a region of a thickness direction cross section of a test piece having a length of 30 mm x width of 10 mm x thickness of 1.0 mm including the polyamide resin composition, a depth of 250 μm ± 8.8 μm from a main surface of the test piece, and a width of 25 μm orthogonal to the thickness direction are observed, a number average value As (μm 2 ) of cross-sectional areas of the particles of the bromine-based flame retardant (B) is less than 0.1 μm 2 .

2. The polyamide resin composition according to claim 1, wherein, a product of a number average of diameters of a circle having the same area as a cross-sectional area of particles of the bromine-based flame retardant (B) observed in the region, and pi, that is, EqD x pi (pm) is less than 1.0 pm.

3. A polyamide resin composition containing a polyamide (A) having a melting point of 280°C or higher, a bromine-based flame retardant (B), an inorganic filler (C), an aromatic vinyl-based copolymer (D), and a colorant (E), the polyamide (A) contains diamine units, 50 to 100 mole% of the diamine units being aliphatic diamine units having a carbon number of 4 to 18, the colorant (E) is at least one of an organic colorant and an inorganic colorant, When the particles of the bromine-based flame retardant (B) in a region of a depth of 250 μm ± 8.8 μm from the main surface of the test piece and a width of 25 μm orthogonal to the thickness direction in the thickness direction cross section of a test piece of 30 mm in length, 10 mm in width, and 1.0 mm in thickness containing the polyamide resin composition are observed, Rs1 (μm) represented by the following formula (1) is less than 0.2 μm 2 Rs1 = (number of particles) / (area of the region) 2 , Rs1 = (bs / as) x As (1) in formula (1), bs / as is a number average of ratios of perpendicular Feret diameters to minimum Feret diameters in Feret diameters of particles of the bromine-based flame retardant (B) observed in the region, and As is the number average of the cross-sectional area of the particles of bromine-based flame retardant (B) observed in the region, in units of pm 2 .

4. The polyamide resin composition according to claim 3, wherein, Rs2 (pm) shown in the following formula (2) is less than 1.7 pm when the particles of the bromine-based flame retardant (B) in the region are observed, Rs2 = (bs / as) x EqD x pi (2) in formula (2), bs / as is a number average of ratios of perpendicular Feret diameters to minimum Feret diameters in Feret diameters of particles of the bromine-based flame retardant (B) observed in the region, and EqD is a number average of diameters of a circle having the same area as a cross-sectional area of particles of the bromine-based flame retardant (B) observed in the region, in pm.

5. The polyamide resin composition according to any one of claims 1 to 4, wherein, DE shown in the following formula (X) is greater than 1, ···(X) In equation (X), ΔE is derived from CIE1976 (L * a * b * The color difference specified in the color system, L * col a * col and b * col The polyamide resin composition is derived from CIE1976 (L * a * b * The color system specified by L * a * and b * L * nat a * nat and b * nat It is a colorless polyamide resin composition that has the same composition as the polyamide resin composition except that it does not contain colorant (E), as specified in CIE 1976 (L). * a * b * The color system specified by L * a * and b * .

6. The polyamide resin composition according to any one of claims 1 to 5, wherein, the organic colorant is at least one selected from the group consisting of an anthraquinone-based dye, a perinone-based dye, an anthrapyridone-based dye, and a phthalocyanine-based dye.

7. The polyamide resin composition according to any one of claims 1 to 6, wherein, the inorganic colorant is at least one selected from the group consisting of carbon black, a metal oxide, a metal sulfide, and a composite metal oxide.

8. The polyamide resin composition according to any one of claims 1 to 7, wherein, the inorganic colorant is at least one selected from the group consisting of a metal oxide, a metal sulfide, and a composite metal oxide.

9. The polyamide resin composition according to any one of claims 1 to 8, wherein, the colorant (E) contains the organic colorant, a content of the organic colorant being 0.0001 to 0.5% by mass with respect to 100% by mass of the polyamide resin composition.

10. The polyamide resin composition according to any one of claims 1 to 9, wherein, the colorant (E) contains the inorganic colorant, a content of the inorganic colorant being 0.001 to 5.0% by mass with respect to 100% by mass of the polyamide resin composition.

11. The polyamide resin composition according to any one of claims 1 to 10, wherein, the bromine-based flame retardant (B) is at least one selected from the group consisting of brominated polystyrene and polybromostyrene.

12. The polyamide resin composition according to any one of claims 1 to 11, wherein, The polyamide (A) contains dicarboxylic acid units, in which 50 mol% or more of the dicarboxylic acid units are terephthalic acid units, and a carbon number 4 to 18 aliphatic diamine constituting the carbon number 4 to 18 aliphatic diamine units is at least one selected from the group consisting of 1,4-butanediamine, 1,6-hexanediamine, 1,9-nonanediamine, 2-methyl-1,8-octanediamine, and 1,10-decanediamine.

13. The polyamide resin composition according to claim 12, wherein, The carbon number 4 to 18 aliphatic diamine is at least one selected from the group consisting of 1,9-nonanediamine and 2-methyl-1,8-octanediamine.

14. The polyamide resin composition according to any one of claims 1 to 13, wherein, The aromatic vinyl-based copolymer (D) contains a structural unit derived from at least one selected from the group consisting of styrene and α-methylstyrene, and a structural unit derived from at least one selected from the group consisting of maleic anhydride and a monoalkyl maleic anhydride having an alkyl group of 1 or more and 3 or less, The glass transition temperature of the aromatic vinyl-based copolymer (D) is 120°C or higher.

15. The polyamide resin composition according to claim 14, wherein, The content of the structural unit derived from at least one selected from the group consisting of maleic anhydride and a monoalkyl maleic anhydride having an alkyl group of 1 or more and 3 or less in the aromatic vinyl-based copolymer (D) is 18 mass% to 50 mass%.

16. The polyamide resin composition according to any one of claims 1 to 15, wherein The weight average molecular weight (Mw) of the aromatic vinyl-based copolymer (D) is 10,000 to 500,000.

17. The polyamide resin composition according to any one of claims 1 to 16, further containing a flame retardant aid (F).

18. The polyamide resin composition according to any one of claims 1 to 17, wherein, containing, relative to 100 parts by mass of the polyamide (A), 25 parts by mass to 70 parts by mass of the bromine-based flame retardant (B), 30 parts by mass to 250 parts by mass of the inorganic filler (C), 0.1 parts by mass to 10 parts by mass of the aromatic vinyl-based copolymer (D), and 0.0005 parts by mass to 20 parts by mass of the colorant (E).

19. A method for producing the polyamide resin composition according to any one of claims 1 to 18, wherein, The polyamide (A), the bromine-based flame retardant (B), the inorganic filler (C), the aromatic vinyl-based copolymer (D), and the colorant (E), and a flame retardant aid (F) added as necessary are melt-kneaded.

20. A molded body which is a molded body of the polyamide resin composition according to any one of claims 1 to 18.

21. The molded body according to claim 20, which is a connector.

22. The molded body according to claim 20 or 21, which is a connector for a vehicle.

Citation Information

Patent Citations

  • Polyamide resin composition

    JP2000186206A

  • Flame-retardant polyamide composition, pellet and molding, and use thereof

    JP2002138197A

  • Flame-retardant polyamide resin composition

    JP2007291250A

  • Polyamide composition and molded product composed of said polyamide composition

    WO2020040191A1